Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2022)
A dataset containing 101044857 species occurrences available in GBIF matching the query: { "and" : [ "BasisOfRecord is Specimen", "HasCoordinate is true", "HasGeospatialIssue is false", "OccurrenceStatus is Present", "Year 1000-2022" ] } The dataset includes 101044857 records from 12900 constituent datasets: 1 records from New genera of Alleculinae (Coleoptera: Tenebrionidae: Alleculinae: Alleculini) from the Oriental Region. Part XI-Vietnalia gen. nov.. 1 records from First report on Paratischeria from Asia (Lepidoptera: Tischeriidae). 5 records from A new species of Andinobates (Amphibia: Anura: Dendrobatidae) from west central Panama. 13 records from A taxonomic review of the genus Amicta Heylaerts, 1881 in North Africa, Near and Middle East (Lepidoptera, Psychidae, Oiketicinae, Acanthopsychini). 3 records from New and little known species of Lepechinella (Crustacea, Amphipoda, Lepechinellidae) and an allied new genus Lepesubchela from the North Atlantic. 4 records from Paragoniosomatinae, a new subfamily of Gonyleptidae (Arachnida: Opiliones) based on a new species from the Chapada Diamantina relict cloud forests, Brazil. 4 records from A revision of the species of the Neoserica (sensu lato) vulpes group (Coleoptera: Scarabaeidae: Sericini). 23 records from Overview of the Anyphaenids (Araneae, Anyphaeninae, Anyphaenidae) spider fauna from the Chocó forest of Ecuador, with the description of thirteen new species. 3 records from Dragmaxia anomala sp. n. (Demospongiae: Halichondrida) from the southwestern Atlantic (Brazil). 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 3 records from Potamotrygon boesemani (Chondrichthyes: Myliobatiformes: Potamotrygonidae), a new species of Neotropical freshwater stingray from Surinam. 8 records from The millipede family Polyxenidae (Diplopoda, Polyxenida) in the faunas of the Crimean Peninsula and Caucasus, with notes on other European Polyxenidae. 5128 records from Spider Mites Collection of Jean Gutierrez. 1 records from The neotype designation for Podismopsis gynaemorpha Ikonnikov, 1911 (Orthoptera: Acrididae). 7 records from Ichneumonid wasps from Madagascar. VI. The genus Pristomerus (Hymenoptera: Ichneumonidae: Cremastinae). 30 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 3 records from Revision of the Central American and Mexican species of the Curtonotum murinum species complex (Diptera: Curtonotidae). 1 records from Redescription of the monotypic genus Cubacanthozomus (Schizomida: Hubbardiidae) and conservation status of its type-species. 1 records from A short taxonomic note on the katydids from the genus Cercoteratura Gorochov, 2019 (Orthoptera: Tettigoniidae: Meconematinae), with a key to species. 1897 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 718 records from Inventario florístico de las Cactáceas del estado de Tamaulipas, México. 276881 records from R. L. McGregor Herbarium Vascular Plants Collection. 2 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 9 records from Three new species of Lecteria Osten Sacken, 1888 (Diptera: Tipulidae) from a scientific survey in Mitaraka (French Guiana). 4 records from Marmacuma samimei gen. et sp. nov., (Peracarida; Cumacea; Nannastacidae) from Tarantian (Upper Pleistocene) sediments from the Sea of Marmara, Turkey. 15 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 10 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 4 records from A new species of Astyanax Baird & Girard (Characiformes: Characidae) from the upper rio Araguaia, Central Brazil. 1904 records from 臺灣特有生物研究保育中心植物標本館(TAIE)苔蘚資料. 3 records from Cryptochrysa Freitas & Penny, a generic homonym, replaced by Titanochrysa Sosa & Freitas (Neuroptera: Chrysopidae). 2125 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 7 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 3 records from A new subspecies in the Turdus nudigenis complex (Aves: Turdidae) from the Cauca River valley of Colombia. 20 records from Colección de Referencia de Poríferos del Museo de Ciencias de la Universidad El Bosque. 1 records from Description of Cephalotes specularis n. sp. (Formicidae: Myrmicinae) - the mirror turtle ant. 15 records from Notes on the Stenus indubius group with descriptions of four new species from China (Coleoptera, Staphylinidae). 498 records from Estudio poblacional del chano norteño, Micropogonias megalops y la curvina Golfina Cynoscion othonopterus (Gilbert) (Pisces: Sciaenidae), especies endémicas del Alto Golfo de California, México. 16052 records from University of Guam Insect Collection. 2 records from Dermaptera of Iran with description of Euborellia angustata sp. nov.. 5 records from Three new species of Pambolus (Braconidae: Pambolinae) from Mexico, with comments on the variation of P. oblongispina Papp. 3986 records from FBIP: What are the impacts of global climate change on arid soil microbial communities?. 2 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 3 records from Graziaedessa anastrephae (Heteroptera: Pentatomidae: Edessinae) a new genus and species collected in Multilure fruit fly traps baited with ammonium acetate and putrescine. 570 records from Zoocenosis of the mole burrows in the forest zone of Western Siberia. 8 records from A new record and two new species of Cryptochironomus Kieffer, 1918 from China (Diptera, Chironomidae). 2 records from Three new species of the barracudina genus Lestidium (Aulopiformes: Paralepididae) from the Indo-West Pacific. 3 records from Universidad de San Carlos de Guatemala - Colección de Porifera. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 1 records from A Scanning Electron Microscopy Study Of The Epiprocts Of Western North American Sweltsa (Plecoptera: Chloroperlidae). 6 records from Revision of world species of the genus Oreiscelio Kieffer (Hymenoptera, Platygastroidea, Platygastridae). 7 records from A revision of African helmeted terrapins (Testudines: Pelomedusidae: Pelomedusa), with descriptions of six new species. 5 records from Hydromedusae observed during night dives in the Gulf Stream. 21 records from The Plecoptera of Panama. II. Two new species, one new country record, and additional locality records of Anacroneuria (Perlidae) from western Panama. 3 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 2516 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche (Plantas). 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 1 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 1 records from New cave-dwelling Plakina (Plakinidae, Homoscleromorpha, Porifera) from Martinique Island (French Antilles). 1056 records from UWIZM Molluscs. 302145 records from CAS Herpetology (HERP). 2 records from Review of Thoreyella Spinola with the description of two new species from Brazil (Heteroptera, Pentatomidae). 9 records from Herbarium specimens of Herbiers Universitaires de Clermont-Ferrand (CLF). 4007 records from MCP-Aves - Coleção de Aves. 1 records from Hidden diversity in European bees: Andrenaamieti sp. n., a new Alpine bee species related to Andrenabicolor (Fabricius, 1775) (Hymenoptera, Apoidea, Andrenidae). 2 records from Three new species of Psyrassa Pascoe, 1866 (Coleoptera, Cerambycidae, Cerambycinae). 34 records from Revision of the French Polycirridae (Annelida, Terebelliformia), with descriptions of eight new species. 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 3606 records from BHZB - Herbário do Jardim Botânico da Fundação Zoo-Botânica de Belo Horizonte. 83 records from Invasive alien species Impatiens glandulifera Royle in the Republic of Karelia. 371 records from orthopteracollections-nhmj-ioj. 2 records from Vascular Plants of Murmansk Region at the Komarov Botanical Institute (LE), St. Petersburg, Russia. 776 records from Bird specimens of Saitama Museum of Natural History. 23 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes (Reptiles). 21 records from Genus Bungona Harker, 1957 (Ephemeroptera: Baetidae) from China, with descriptions of three new species and a key to Oriental species. 1 records from Review of the millipede tribe Polydrepanini, with the description of a new species from Kerala state, southern India (Diplopoda, Polydesmida, Paradoxosomatidae, Alogolykinae). 870 records from Vertebrados terrestres de San Juan de Camarones, Durango. 2 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 6 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 617 records from Mycology collection, Norwegian Forest and Landscape Institute. 203 records from New Records of ground beetles for Colombia (Coleoptera: Carabidae). 43908 records from Mammalia (Luomus). 17 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 6 records from New seriated Amathia species in Japan, with a redescription of A. acervata Lamouroux, 1824 (Bryozoa: Ctenostomata). 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 4 records from Le genre Argentina Hill (Rosaceae) en Nouvelle-Guinée: une espèce et une combinaison nouvelles. 8 records from The megisthanid mites (Mesostigmata: Megisthanidae) of Australia. 537 records from Middlebury College Insect Collection: Bees (Anthophila). 6 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 13129 records from Colección de Solanales del Museo Botánico CORD - IMBIV. 35 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 269700 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Herbario). 17 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 6764 records from Actualización de las bases de datos de las colecciones de plantas vasculares y macromicetos del herbario de la UJAT (Plantas). 46 records from Brachymelecta Linsley, 1939, previously the rarest North American bee genus, was described from an aberrant specimen and is the senior synonym for Xeromelecta Linsley, 1939. 3 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 3 records from Two new species of flavomaculata-group of the genus Macrophya Dahlbom (Hymenoptera: Tenthredinidae) from China. 1 records from Stylogomphus thongphaphumensis (Odonata: Anisoptera: Gomphidae), a new gomphid dragonfly and the first record of S. malayanus Sasamoto, 2001 from Thailand. 160 records from UWIZM Anoles. 1 records from A contribution to the knowledge of Dermestidae (Coleoptera) from Guatemala. 4 records from A new species of Decimiana Uvarov from Brazil, with updated key to species and remarks on their geographic distribution (Mantodea: Acanthopidae, Acanthopinae). 28 records from Huangilene, a new genus for the Miltochrista alikangiae (Strand, 1917) species-group, with descriptions of three new species from Indochina, continental China and Taiwan (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 2 records from Macaronesian Muscidae (Diptera). I. The genus Hebecnema Schnabl with description of a new Canarian endemic species and a review of the European fauna. 2 records from Molecular phylogenetics, PCA, and MFA recover a new species of Cyrtodactylus (Squamata: Gekkonidae) from an isolated sandstone massif in northwestern Cambodia. 20 records from A new genus and five new species of Neocoelidiinae leafhoppers from Brazil (Insecta: Hemiptera: Cicadellidae) with a key to males. 9 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 2 records from hips of Epidrepanus within the subtribe Drepanocerina (Coleoptera: Scarabaeidae: Scarabaeinae: Oniticellini), with the description of two new species. 31 records from Records of the Victorian Conservation Seedbank. 5 records from Orthoptera Tettigoniidae as indicators of biodiversity hotspots in the Guinean Forests of Central and West Tropical Africa. 1 records from Revision of the genus Lamprima Latreille, 1804 (Coleoptera: Lucanidae). 51 records from Diversity of beetles associated with watermelon crops Citrullus lanatus (Thunb.) Mats. in the region of Ouargla (southern Algeria). 2 records from The geometrid moths of Ethiopia I: tribes Pseudoterpnini and Comibaenini (Lepidoptera: Geometridae, Geometrinae). 2 records from First study of the Polycladida (Rhabditophora, Platyhelminthes) from the Pacific Coast of Costa Rica. 59788 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 3 records from Demoulinia Gillies 1990 and two unnamed genera of the plesiomorphon Protopatellata (Ephemeroptera, Baetidae) from South Africa. 111168 records from The digitization of plant specimens of NTU. 192 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 4 records from Carcinoplax fasciata, a new species of deep-water goneplacid crab from southwestern India (Crustacea: Decapoda: Brachyura: Goneplacoidea). 10 records from Review of the dwarf Glossogobius lacking head pores from the Malili lakes, Sulawesi, with a discussion of the definition of the genus.. 10000 records from 2020_biodiversity_information_specimen. 145 records from The genusParascepsis Dognin, 1923 (Lepidoptera, Erebidae, Arctiinae, Ctenuchina) in Peru, with the description of three new species, a new combination and their geographical distributions. 13 records from Four new species of Phrynus, Lamarck (Arachnida: Amblypygi) from Mexico. 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 2 records from Orientatractis brycini sp. nov. (Nematoda: Atractidae) from characiform freshwater fishes in Gabon, Africa. 77689 records from The Himalayan Uplands Plant database (HUP Version 1). 5 records from Three new minute leaf litter beetles discovered by citizen scientists in Maliau Basin, Malaysian Borneo (Coleoptera: Leiodidae, Chrysomelidae). 5 records from Two new littoral species of the genus Anurida Laboulbène, 1865 (Collembola, Neanuridae) from the Pacific coast of Asia. 852 records from Royal BC Museum - Herpetology Collection. 3 records from Two new and one newly recorded species of Polypedilum Kieffer 1912 with DNA barcodes from Oriental China (Chironomidae: Diptera). 3 records from New data on the oriental Xantholinini. 36. Description of the male of Thyreocephalus elegantissimus BORDONI, 2012 and new records (Coleoptera, Staphylinidae) 253 ° contribution to the knowledge of the Staphylinidae. 375 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 1308 records from National Museum of Natural Science. 426 records from University of Alberta Museum of Zoology Ornithology Collection (UAMZ). 26 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 39 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 30 records from Collections ichtyologiques et herpétologiques (BOUM). 2 records from A new species of the genus Takydromus (Squamata, Lacertidae) from southwestern Guangdong, China. 3 records from Impatiens bullatisepala (Balsaminaceae), a new species from Guizhou, China. 15040 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 3 records from A new madicolous species of Nilotanypus Kieffer (Diptera: Chironomidae) from Amazon region, northwestern Brazil. 5 records from First record of the genus Tanaostigma (Hymenopteraı Chalcidoideaı Tanaostigmatidae) from the Afrotropical region with description of three new species. 1 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 1 records from The giant “ penis ” of a newly described species in the subgenus Scotoconiopteryx from Peru (Neuroptera: Coniopterygidae: Coniopteryginae: Coniopteryx). 122 records from Policládidos de la Península de Yucatán. 9 records from Taxonomic revision of Brazilian genus Tyrannoseira Bellini & Zeppelini, 2011 (Collembola, Entomobryidae, Seirinae). 14 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 5 records from A mountain of millipedes VI. New records, new species, a new genus and a general discussion of Odontopygidae from the Udzungwa Mts, Tanzania (Diplopoda, Spirostreptida, Odontopygidae). 5376 records from Lichens of North-Eastern Poland. 1 records from Sarcocheilichthys vittatus, a new species of gudgeon (Teleostei: Cyprinidae) from the Poyang Lake Basin in Jiangxi Province, South China. 8 records from Morphological differences between Stenocionops furcatus (Olivier, 1791) and S. coelatus (A. Milne-Edwards, 1878) (Crustacea, Decapoda, Brachyura, Majoidea). 10 records from Anmerkungen zur Gattung Dapsa L, 1829 (Coleoptera, Endomychidae). 2777 records from artsprosjektet_53-12_enchytraeidae. 2 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 7 records from Cochlostoma revised: the subgenus Lovcenia Zallot et al., 2015 (Caenogastropoda, Cochlostomatidae). 609 records from Arácnidos - Miriápodos de la expedición al Río Apaporis - Proyecto Colombia BIO. 2 records from South American Leaf-Cutter Bees (Genus Megachile) Of The Subgenera Rhyssomegachile And Zonomegachile, With Two New Subgenera (Hymenoptera: Megachilidae). 4 records from Moriphila furva gen. and sp. nov. (Hemiptera: Psylloidea: Homotomidae), a new jumping plant-louse from Korea associated with Morus australis (Moraceae). 95 records from Pycnogonida collection from the Museu Nacional de História Natural e da Ciência da Universidade de Lisboa, Portugal. 41 records from Cochlostoma revised: the subgenus Clessiniella Zallot et al., 2015 (Caenogastropoda, Cochlostomatidae). 145 records from A checklist of the non-leaf-cutting fungus-growing ants (Hymenoptera, Formicidae) from Colombia, with new biogeographic records. 232 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 87 records from Morphological and anatomical investigation of New Caledonian graminoid Dendrobium (Orchidaceae) with the description of two new species. 21 records from Some lesser known silent crickets (Orthoptera: Gryllidae: Euscyrtinae) from the hilly tracts of India. 9 records from A new species of Panaqolus (Siluriformes: Loricariidae) from the rio Madeira basin with remarkable intraspecific color variation. 5 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 14 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 19 records from Universidad de San Carlos de Guatemala - Colección de Equinodermos. 1 records from Two new species and ten new records of Heteroptera from Turkey, including the first record of the potential alien Campylomma miyamotoi in the Western Palaearctic. 5 records from Description of the first Caribbean Oscarellidae (Porifera: Homoscleromorpha). 37 records from Living Cirripedia. 7 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 3 records from Studies in Mexican Grasshoppers: Liladownsia fraile, a new genus and species of Dactylotini (Acrididae: Melanoplinae) and an updated molecular phylogeny of Melanoplinae. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 959 records from Naturhistorisches Museum Mainz, Botanical Collection. 2 records from Updating the knowledge of the flower flies (Diptera: Syrphidae) from Chile: Illustrated catalog, extinction risk and biological notes. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 224 records from Distribución potencial de pargos en el Pacífico mexicano. 5 records from Taxonomic notes on the genus Sinodrepanus Simonis, 1985, with description of the male of S. falsus (Sharp, 1875) (Coleoptera: Scarabaeidae: Oniticellini). 1 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 1201 records from Hormigas (Hymenoptera: Formicidae) del Centro de Colecciones Biológicas de la Universidad del Magdalena. 1195 records from Cryptobiont assemblages's dataset of coral reefs using ARMS in B10 Reef and Mahahual Reef of the Great Caribbean. 1 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 2 records from Modelaje de la distribución potencial de 10 especies de anfibios y reptiles en riesgo de extinción con escasos registros de presencia (PLECHA). 2 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 2 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 3469 records from Estonian University of Life Sciences Institute of Agricultural and Environmental Sciences Department of Plant Protection. 25 records from Five new species of Englerophytum K. Krause (Sapotaceae) from central Africa. 9434 records from University of Nebraska State Museum Birds Collection. 2 records from First record of the genus Eriopisella Chevreux, 1920 (Crustacea, Amphipoda, Senticaudata, Eriopisidae) from Australia, with the description of a new species, Eriopisella moretoni sp. nov.. 28608 records from University of California Santa Barbara Invertebrate Zoology Collection. 4211 records from Colección de Laurales, Liliales, Lycopodiales, Magnoliales y Malpighiales del Museo Botánico CORD - IMBIV. 14 records from Two new species of Nullana from southern Brazil (Hemiptera: Cicadellidae: Gyponini) with key to males. 2222 records from IRAD Cameroon insect collection. 381 records from The Reduviidae (Hemiptera: Heteroptera) of Alabama, with a morphological key to species. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 2077 records from Pierid butterfly specimens (Part 3: Appias, Elodina, Leuciacria, Udaiana) at Museum Zoologi Bogor, Indonesia. 4 records from Discovery of the male of Colletes yanruae from Yunnan, China (Hymenoptera: Apoidea: Colletidae). 2 records from Vietnamella chebalingensis, a new species of the family Vietnamellidae (Ephemeroptera) from China based on morphological and molecular data. 8 records from On a collection of deep-water shrimp (Crustacea, Decapoda) from the Dutch Caribbean, with the description of a new species of Pseudocoutierea. 8 records from Synopsis of Lestes from Brazil with description of Lestes demarcoi sp. nov (Zygoptera: Lestidae). 183 records from Mammifères (sauf Chiroptères) du Muséum d'Histoire Naturelle de la ville de Bourges (BOUM). 69479 records from Entomology Collection at the Natural History Museum of Utah. 1552 records from Vertebrados terrestres del Corredor Biológico Sierra Madre del Sur, Chiapas, México. 12 records from Taxonomic review of the genus Parastenolechia Kanazawa (Lepidoptera, Gelechiidae, Litini) from Mainland China, with descriptions of six new species. 20 records from Mollusc specimens of Parthenon Tama History Museum (PTHM). 5236 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 2 records from Morphological and molecular characterization of Klossnema viguerasi n. sp (Nematoda: Oxyuridomorpha: Hystrignathidae) from a Cuban passalid beetle (Coleoptera: Passalidae), first record of the genus for Cuba. 3202 records from Taxonomic, geographical and temporal coverage of Rubiaceae specimens at DSM herbarium, University of Dar es Salaam. 5 records from New genus, new species and new records in Lamiinae (Coleoptera, Cerambycidae). 135 records from Hartland Nature Club Lepidoptera Collection. 4 records from Symphyla Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 85741 records from ALCB - Herbário Alexandre Leal Costa. 2 records from Herbarium specimens of Limoges university (LIMO). 8 records from Xenosinelobus balanocolus, a new tanaidid genus and species (Crustacea: Peracarida: Tanaidacea) from barnacles on intertidal rocky shores and seawalls in the Singapore Strait. 3693 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 86014 records from Fish specimens of Kagoshima University Museum. 1 records from Ecsenius niue, new species of blenniid fish, and new distribution records for other species in the Opsifrontalis species group.. 2 records from A revision of Colletes Latreille (Hymenoptera: Colletidae: Colletinae) from Brazil, Paraguay and Uruguay. 104 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 11 records from Grewia hispidissima Wahlert, Phillipson & Mabb., sp. nov. (Malvaceae, Grewioideae): a new species of restricted range from northwestern Madagascar. 93 records from New records of Crabronidae fauna (Hymenoptera, Apoidea) of Tunisia. 7 records from Plathelminthes - SMF. 3 records from Epidendrum dayseae, a new species of Orchidaceae (Laeliinae) from northern Brazil. 1 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 10071 records from Insect specimens of Rikuzen-Takata City Museum. 1 records from Neopedies taimensis n. sp. of Brazilian Dichroplini (Orthoptera: Acrididae, Melanoplinae) from Rio Grande do Sul, Brazil. 1 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 3 records from A new alpine skink species (Scincidae: Eugongylinae: Oligosoma) from Kahurangi National Park, New Zealand. 18 records from Six new species of Orthochirus Karsch, 1892 from Iran (Scorpiones Buthidae). 3 records from Taenionema Jeanae, A New Species Of Stonefly From Southern California (Plecoptera: Taeniopterygidae). 864 records from Caracterizando la diversidad de especies con códigos de barras del ADN en un grupo de avispas parasitoides: un caso de estudio en un área natural protegida mexicana. 12249 records from Cowan Tetrapod Collection - Mammals. 1811 records from Actualización de la información sobre los maíces criollos de Oaxaca. 11 records from High diversity and endemism in the genus Cautires Waterhouse, 1879 (Coleoptera: Lycidae) from the Malay mountain forests, with the descriptions of fourteen new species. 3 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 88 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 36 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 184 records from Bark and Ambrosia Beetles of Vermont from Thomas H. Atkinson. 8 records from The lestevoides species group of the genus Geodromicus Redtenbacher, 1857 (Insecta: Coleoptera: Staphylinidae: Omaliinae). 7 records from The genus Sicoderus Vanin 1986 (Coleoptera: Curculionidae: Curculioninae: Erodiscini) in the West Indies. 3 records from Vasopora ceramica n. gen., n. sp. - a new abyssal cyclostome bryozoan from polymetallic nodules in the Russian exploration area, Clarion-Clipperton Fracture Zone, eastern Pacific Ocean. 205870 records from University of Minnesota Insect Collection. 16 records from Insect Collections of Okomu National Park- Nigeria. 132472 records from ARABEL - Arachnologia Belgica. 14 records from A taxonomic revision of the genus Hexarhopalus (Coleoptera, Tenebrionidae Cnodalonini) from China. 1 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 8 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 3 records from The family Opilioacaridae (Acari: Parasitiformes) in Argentina, with description of two new species. 1 records from Capnia Shasta, A New Species In The Californica Group From Northwestern California (Plecoptera, Capniidae). 1 records from A new species of Isometopus from Iran (Hemiptera: Heteroptera: Miridae: Isometopinae). 74 records from Ohio Wesleyan University Mammal Specimens (Arctos). 2599 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 15336 records from LSUMZ (LSU MNS) Fishes Collection. 60961 records from MLZ Bird Collection (Arctos). 4 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 11 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 5 records from New records and updated distribution of the ant-like jumping spider genus Zuniga Peckham & Peckham, 1892 (Salticidae: Salticinae: Sarindini) in the Neotropics. 39 records from Taxonomic revision of the Neotropical genus Himantigera James, 1982 (Diptera: Stratiomyidae: Sarginae), including the description of two new species and a key to the known species. 4 records from Coeliccia lecongcoi sp. nov., a new damselfly from the Central Highlands of Vietnam (Odonata: Zygoptera: Platycnemididae). 1141 records from Ornithologie Federsammlung - SNSD. 1 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 2 records from A new species of Trachylepis (Squamata: Scincidae) from Central Africa and a key to the Trachylepis of West and Central Africa. 22 records from LISU Lichen collection. 385 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 4 records from A remarkable new species of Micropeza Meigen (Diptera: Micropezidae) from Caatinga biome, Brazil. 80976 records from Herbarium (ICEL). 1 records from A new species of Pristomerus Curtis, 1836 (Hymenoptera, Ichneumonidae Cremastinae) and key to the known species in Iran. 59783 records from Herbarium Senckenbergianum (FR) - Fungi. 1994 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 5 records from New species, redescriptions and a new combination of Acanthocyrtus Handschin, 1925 and Amazhomidia Cipola & Bellini, 2016 (Collembola, Entomobryidae, Entomobryinae). 81 records from Mamíferos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 4 records from A new species of the ant genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae) from the Caribbean region. 4 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 3879 records from Inventario de la mastofauna en las reservas de la biosfera Desierto del Vizcaíno y Valle de los Cirios. 2 records from Limnebius (Limnebius) agnieszkae sp. n. from the Crimean Peninsula (Coleoptera: Hydraenidae). 47 records from Inventario de corales pétreos, asteroideos, equinoideos y peces óseos de arrecifes de la costa de Jalisco, Colima y Michoacán. 4 records from A ghost in the salt: A new species of halotolerant tube-web spider in the genus Ariadna (Araneae: Segestriidae). 80 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 17 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 7 records from First record of the genus Agnara (Isopoda: Oniscidea) from Iran with descriptions of two new species. 25 records from Leiolima iberica, a new harvestman genus and species from the Iberian Peninsula (Arachnida, Opiliones, Sclerosomatidae). 2 records from Umbellula pomona sp. nov., a new sea pen from Mar del Plata Submarine Canyon (Cnidaria: Octocorallia: Pennatulacea). 1 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 51 records from Anfibios y reptiles de la expedición en el páramo de Pisba, Boyacá - Proyecto Boyacá BIO. 11 records from The InBIO Barcoding Initiative Database: Portuguese Stag beetles (Coleoptera, Lucanidae). 3 records from Taxonomic review of the genus Dascillus Latreille, 1797 in the Western Palaearctic (Coleoptera: Dascillidae). 1680 records from Universidad del Valle de Guatemala - Colecciones Biológicas - Peces. 2 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 2 records from Two new species of Rhiginia Stål, 1859, with taxonomical notes on species in the “ cruciata-group ” of this genus and an updated key to the New World genera of Ectrichodiinae (Heteroptera, Reduviidae). 1 records from Reptilia ZMK. 21353 records from Fungal occurrences from the Basque Country and neighbouring areas: ARAN-Fungi. 12 records from New records of Trichoceridae (Diptera) from the island of Mallorca ​. 1290 records from Diversity of Spiders from Azorean Trails. 1 records from The bees of Lebanon (Hymenoptera: Apoidea: Anthophila). 4709 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 8 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 366 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 15 records from Tardigrad collection of the National Museum of Nature and Science. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 4 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 2 records from Revision of the genus Sinobathyscia Perreau (Coleoptera, Leiodidae, Cholevinae) from China, with description of a new species. 3 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 8 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 20625 records from Herbier Louis-Marie (QFA) - Collection de lichens. 86 records from Integrative taxonomy of the genus Dyscolus (Coleoptera, Carabidae, Platynini) in Ecuadorian Andes. 5 records from Taxonomic review of the species of Helina R. - D. (Diptera: Muscidae) from Andean-Patagonian forests. 3 records from Review of Glaphyrosoma (Orthoptera: Stenopelmatoidea: Anostostomatidae) including new species and biological information. 115 records from Swedish Malaise Trap Project (SMTP) - Vespinae. 2 records from Dolichopus nimbatus Parent, 1927 revisited, with two new synonyms (Diptera: Dolichopodidae). 26548 records from Actualización de la base de datos del estado de Morelos de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 47 records from The Philippine hair wax spiders and their relatives: revision of the Pholcus bicornutus species group (Araneae, Pholcidae). 1 records from A new Rhopalomeris species (Diplopoda: Glomerida: Glomeridae), and notes on the phylogenetic relationships between glomeridans in Vietnam. 5 records from Taxonomic review and distribution of the genus Vespula Thomson, 1869 (Hymenoptera: Vespidae: Vespinae) from Vietnam. 18 records from Chaoborus flavicans Meigen (Diptera, Chaoboridae) is a complex of lake and pond dwelling species: a revision. 3 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 3 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 12 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 14 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 1 records from Notes on two species of the genus Atemnus Canestrini (Pseudoscorpiones: Atemnidae) from China. 2 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 2 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 34 records from Swedish Malaise Trap Project (SMTP) - Dermaptera. 11985 records from Observations du Conservatoire botanique national du Bassin parisien.. 177 records from Echinodermata specimens of Kuroshio Biological Research Foundation. 7247 records from Colecção Entomológica IIA. 56 records from Colección de Zoología Universidad Icesi: Insectos. 46527 records from TNHC Herpetology Collection. 69 records from ZUEC-POR - Coleção de Porifera do Museu de Zoologia da UNICAMP. 108 records from Inventario de la biota terrestre (florístico) y marina (invertebrados, peces y macroalgas bentónicos) del parque nacional Isla Isabel (Plantas). 2351 records from Museu Darder de Banyoles. 2 records from Two new species of Acontias (Acontinae, Scincidae) from the Mpumalanga Highveld escarpment of South Africa. 317 records from Swiss National Cicadidae Databank. 4 records from More new Diplotrema earthworm species from southern Mexico (Annelida, Crassiclitellata, Acanthodrilidae, Acanthodrilinae). 1 records from Ovilyra, a new genus of leucosiid crab (Crustacea: Decapoda: Brachyura) from the West Pacific. 316 records from Moss species from Heard Island, 1987 and 2000. 1076 records from DMNS Egg Collection (Arctos). 289 records from Odonata del Museo de Entomología de la Universidad del Valle. 495 records from USFWS Bee surveys - Sandbar WMA, VT 2018. 1 records from A new species of Anteon from Zimbabwe (Hymenoptera, Dryinidae). 808 records from A taxonomic revision of the African genus Desplatsia Bocq. (Malvaceae - Grewioideae). 13159 records from Lepidopterous specimens of Yamagata Prefectural Museum. 15 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 6 records from Dactylobasis gen. nov. from Colombia, a new genus of Zygoptera with Teinobasini affinities (Odonata: Coenagrionidae). 3 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 1 records from The larva and pupa of Potamyia flavata (Banks 1934) (Trichoptera: Hydropsychidae): Description, life cycle, and notes on its biology. 193 records from The diversity of the genus Aricidea (Polychaeta: Paraonidae) from the Sea of Marmara, with descriptions of two new species and two new records for the Mediterranean fauna. 14 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 1 records from Contribution to the genus Okinawepipona Yamane (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with description of a new species. 1 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 380 records from Orthoptera - SMF. 4 records from Cyphocharax boiadeiro, a new species from the upper rio Araguaia, Amazon basin, Brazil (Characiformes: Curimatidae). 9 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 4 records from Priocharax nanus, a new miniature characid from the rio Negro, Amazon basin (Ostariophysi: Characiformes), with an updated list of miniature Neotropical freshwater fishes. 17 records from Amphibian and Reptile species occurrence records in the Tana River Basin, Kenya. 2 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 4 records from COI mtDNA barcoding and morphology for the description of a new species of ricinuleid of the genus Pseudocellus (Arachnida: Ricinulei: Ricinoididae) from El Triunfo Biosphere Reserve, Chiapas, Mexico. 1 records from Registro de Chromolaena tacotana asociado al proyecto: Relación estructura-actividad anti-cáncer de flavonoides sobre líneas celulares cancerosas. 1702 records from BioGIS - Bryophytes - HUJ collections. 2 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 27 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 2 records from Bambusa gurgandii K. M. Wong & M. H. Diep (Poaceae, Bambusoideae), a new species of bamboo from Vietnam. 38681 records from Herbarium Universitatis Daugavpiliensis. 5 records from Hyleina kaphetea, a new genus and species of clearwing moths from tropical Africa (Lepidoptera: Sesiidae: Sesiini). 1301 records from Universidad del Valle de Guatemala - Colección de Artrópodos (UVGC). 3 records from Validation of Stenus (Hypostenus) primivenatus and Stenus (Hypostenus) yiae (Coleoptera, Staphylinidae, Steninae). 1 records from Loneura Navás (Psocodea: Psocomorpha: Ptiloneuridae): new species from Brazil, and description of the female of Loneura maracaensis Garcia Aldrete, with a checklist of all known species of the genus. 9 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 48 records from Swedish Malaise Trap Project (SMTP) - small parasitic aculeate families. 1 records from Megaluropidae *. 16461 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 2 records from Myxiops aphos, new characid genus and species (Characiformes: Characidae) from the rio Lençóis, Bahia, Brazil. 6178 records from Plecoptera. 3 records from MtDNA differentiation and taxonomy of Central Asian racerunners of Eremias multiocellata - E. przewalskii species complex (Squamata, Lacertidae). 2 records from Synaptus iranicus sp. nov., a second species of the genus Synaptus Eschscholtz, 1829 from Iran (Coleoptera: Elateridae) discovered by an integrative approach. 1 records from Redescription of Luetkenia elongata (Copepoda: Siphonostomatoida: Pandaridae), an Ectoparasite of Luvarus imperialis (Actinopterygii: Perciformes: Luvaridae), with a New Record from Japanese Waters. 15 records from A revision of the Chilean Brachyglutini – Part 3. Revision of Achilia Reitter, 1890: A. frontalis species group (Coleoptera: Staphylinidae: Pselaphinae). 2 records from A new species of and a new transfer from the millipede genus Polydrepanum Carl, 1932 (Polydesmida, Paradoxosomatidae, Polydrepanini). 5 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 5 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 5 records from New Species Of Neoperla Needham And Phanoperla Banks (Plecoptera: Perlidae) From The Philippine Islands. 7 records from New Polypheretima and Pithemera (Oligochaeta: Megascolecidae) species from the Mt. Malindang Range, Mindanao Island, Philippines. 10 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 3 records from First record of the subfamily Brachycyrtinae (Hymenoptera, Ichneumonidae) from continental Africa, with description of three new species. 167 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 8 records from Re-description of Coeliccia erici Laidlaw, and the description of Coeliccia sameerae sp. nov. from Peninsular Malaysia (Odonata: Zygoptera: Platycnemididae). 2 records from Hagneia kallea gen. and sp. nov. (Hemiptera: Fulgoromorpha: Ricaniidae) from North Vietnam. 3 records from Argiope hoiseni, a new species of the spider genus Argiope (Araneae, Araneidae) from Peninsular Malaysia based on morphology and molecular analyses. 11 records from New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records. 7 records from First record of the genus Phoxoserphus Lin, 1988 (Hymenoptera: Proctotrupidae) from Japan. 14 records from NZCS Brownsberg Nature Park Monitoring. 962 records from Bees in the UVM Zadock Thompson Zoological Collection. 2277 records from La flora útil de dos comunidades indígenas del Valle de Tehuacán-Cuicatlán: Coxcatlán y Zapotitlán de las Salinas, Puebla. 4358 records from Collection Mollusca SMF. 20 records from A description of the flea species Paractenopsyllus madagascarensis n. sp. and the female sex of Paractenopsyllus raxworthyi Duchemin & Ratovonjato, 2004 (Siphonaptera, Leptopsyllidae) from Madagascar with a key to the species of Paractenopsyllus. 4 records from Two new species of fanged frogs from Peninsular Malaysia (Anura: Dicroglossidae). 35 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 19 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 1 records from Pseudaeginella telukrimau sp. n., a new species of caprellid (Crustacea: Amphipoda) from Malaysia. 9156 records from NEON Biorepository Carabid Collection (DNA Extracts). 2 records from A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini). 5 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 11 records from A New Perlodes Species And Its Subspecies From The Balkan Peninsula (Plecoptera: Perlodidae). 23150 records from US herbarium - Smithsonian Institute - Amostras Brasileiras Repatriadas - Herbário Virtual REFLORA. 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 10136 records from Inventario de Hymenóptera; parasítica en México. 4130 records from UAM Herbarium (ALA), Algae Collection (Arctos). 8561 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 1 records from A new genus of mongoliulid millipedes from the Far East of Russia, with a list of species in the family (Diplopoda, Julida, Mongoliulidae). 2 records from New and interesting palpigrades (Arachnida, Palpigradi) of the genera Koeneniodes Silvestri, 1913 and Prokoenenia Börner, 1901 from Asia. 4687 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 5 records from Hydraena (s.str.) dinarica, new species (Coleoptera: Hydraenidae) along with further records of Hydraena spp. from Durmitor National Park, Montenegro and comments on the DNA barcoding problem with the genus. 709 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 2 records from Caroperla brevihamata (Plecoptera: Perlidae), a new stonefly species from Guangxi Zhuang Autonomous Region of southern China. 3 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 6 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 1533 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 847 records from Sistemática y biogeografía del género Reithrodontomys (Rodentia: Muridae). 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 2 records from The identity of Aplocheilus andamanicus (Köhler, 1906) (Teleostei: Cyprinodontiformes), an endemic Killifish from the Andaman Islands, with notes on Odontopsis armata van Hasselt. 1 records from Multiple lines of evidence reveal a new species of Krait (Squamata, Elapidae, Bungarus) from Southwestern China and Northern Myanmar. 82 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 357 records from Colección Botánica-Herbario. Museo de Ciencias Naturales y Antropológicas “Juan Cornelio Moyano” (Mendoza, Argentina). 3 records from Three new species of eriophyoid mites of the tribe Phyllocoptini Nalepa (Eriophyoidea: Eriophyidae) from Shaanxi, China. 456 records from Lucanidae. 29 records from New species, synonymy and records of Endomia and Stenidius (Coleoptera: Anthicidae) from Asia. 1 records from Synonymies, new records, and new species in Cerambycinae (Coleoptera Cerambycidae). 1 records from Un Pterostylis R. Br. nouveau (Orchidaceae, Orchidoideae, Cranichideae) de Nouvelle-Calédonie. 27268 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 70 records from Birds Specimens of Akita Prefectural Museum. 3 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 2191 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina (Crustáceos). 9 records from Urochordeumatidae Silvestri, 1909, a millipede family endemic to Washington State, USA (Chordeumatida, Striariidea, Striarioidea). 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 1 records from Three endemic Aphaenogaster from the Siculo-Maltese archipelago and the Italian Peninsula: part of a hitherto unrecognized species group from the Maghreb? (Hymenoptera: Formicidae: Myrmicinae). 2 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 43610 records from Sistematización del Herbario Nacional Forestal Biól Luciano Vela Gálvez. 32 records from MSUM Ichthyology and Herpetology Collections. 24 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 184857 records from Allan Herbarium (CHR). 60363 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 3 records from Pempheris bexillon, a new species of sweeper (Teleostei: Pempheridae) from the Western Indian Ocean. 1 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 22 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 22 records from Schwedische Oribatei (Acari). III.. 14043 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 15 records from Two new sympatric species of Stenocercus (Squamata: Iguania) from the inter- Andean valley of the Mantaro River, Peru. 1123 records from Odonata Specimens of Yamaguchi prefectural Yamaguchi Museum. 14218 records from Coleção Entomológica Moure e Costa. 1 records from MVZ Herp Observations (Arctos). 1 records from New records of benthic hydroids (Cnidaria: Hydrozoa) from the coast of Oaxaca, Mexico. 8 records from The InBIO Barcoding Initiative Database: Ypsolopha rhinolophi sp. nov. (Lepidoptera: Ypsolophidae), a new species from Portugal and France unveiled by bats. 4166 records from Línea base general de hormigas para el valle medio del Magdalena - VMM. 315 records from Distribution of xylotrophic fungi of the genus Daedaleopsis in the Asian part of Russia from 1978 to 2019. 1 records from A new Portholefish of the genus Diplophos (Stomiiformes: Gonostomatidae) from the western Pacific Ocean. 5 records from A new Oreonetides Strand, 1901 from the Russian Far East (Araneae, Linyphiidae). 2 records from Revision of the Afrotropical genus Susua Lugo-Ortiz & McCafferty 1998 (Ephemeroptera: Baetidae: Protopatellata). 82020 records from SA Flora (BDBSA). 13 records from Coleção de Coleoptera da Universidade de Brasília. 5044 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 1 records from The immature stages of Phylloicus obliquus Navás, 1931 (Insecta: Trichoptera: Calamoceratidae). 2 records from A new genus of the mite family Scutacaridae (Acari: Heterostigmata) associated with Trinervitermes trinervoides (Isoptera: Termitidae) from South Africa. 2 records from The first record of the family Chloroperlidae (Plecoptera) from the Guangxi Zhuang Autonomous Region of southern China, with description of a new species of Sweltsa Ricker, 1943. 6 records from A new western Atlantic snapping shrimp of the Alpheus macrocheles group (Caridea, Alpheidae) revealed by morphological, molecular and color data. 23 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 7296 records from Marie-Victorin Herbarium (MT) - Bryophytes. 2 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 1 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 13 records from Bostryx tortoranus (Doering, 1879) species complex (Gastropoda: Stylommatophora: Bulimulidae), a review of taxonomy and distribution of endemic species from Argentina. 5 records from New records of two butterflies of the genus Polyommatus Latreille, 1804 (subgenus Agrodiaetus Hübner, 1822) (Lepidoptera: Lycaenidae) from Iraq. 4 records from On the taxonomy of the subgenera Cyabarda Karisch, 2013, Idiovulpecula Karisch, 2013 and Paravulpeculella Karisch, 2013 of the genus Cyana Walker, 1854, with descriptions of three new species from Africa (Lepidoptera, Erebidae, Arctiinae, Lithosiini). 3 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 1 records from New records of eriophyoid mites from Iran (Acari: Trombidiformes: Eriophyoidea) and a description of a new Brevulacus Manson species. 12 records from Fiocruz/CAVAISC - Coleção de Artrópodes Vetores Ápteros de Importância em Saúde das Comunidades. 14472 records from Biodiversidad mastozoológica del Eje Volcánico Transversal. 6 records from HSU Wildlife Birds. 2 records from Two new species of Aphelochaeta (Annelida: Polychaeta: Cirratulidae) from Korean waters. 77254 records from Odonata Central. 2936 records from Intermountain Herbarium (fungi, not lichens), Utah State University. 6 records from Two new species of Comanthera (Eriocaulaceae) from Bahia, Brazil. 3 records from Description of Coeliccia lephuocdieui sp. nov. from the Central Highlands of Vietnam (Odonata: Zygoptera: Platycnemididae) with notes on its congeners. 517 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 2799 records from La Colección Herpetológica de la Estación de Biología Tropical Los Tuxtlas, Veracruz. 87097 records from Mammalogy Collection - Royal Ontario Museum. 2 records from Rivulus kayapo n. sp. (Teleostei: Cyprinodontiformes: Rivulidae): a new killifish from the serra dos Caiapós, upper rio Araguaia basin, Brazil.. 1 records from Dressed in black. A New Ansonia Stoliczka, 1870 (Lissamphibia: Anura: Bufonidae) from Gunung Murud, Sarawak, East Malaysia (Borneo). 10 records from Contribution to the taxonomic knowledge of Ampharetidae (Annelida) from Antarctica with the description of Amage giacomobovei sp. nov.. 7 records from Parascolopsis akatamae, a new species of dwarf monocle bream (Perciformes Nemipteridae) from the Indo-West Pacific, with redescription of closely related species P. eriomma. 90964 records from CAS Entomology (ENT). 5110 records from Naturalis Biodiversity Center (NL) - Pisces. 24 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 320 records from Marine algal (seaweed) flora of Formigas Islets, Azores. 1222 records from Ichneumonidae (Hymenoptera) de la reserva de la biosfera El Cielo, Tamaulipas. 5 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 502 records from PACA-Bryophytes - Herbarium Anchieta - Aloysio Sehnem. 316 records from Myxomycetes collection of the University of Eastern Finland. 20 records from New data on the fauna of China, part I: the taxonomy of the millipede family Julidae (Diplopoda). 53 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 5 records from The Endemic Sulawesi Fish Genus Lagusia (Teleostei: Terapontidae). 1 records from Incarvillea uniflora (Bignoniaceae), a new species from Hengduan Mountains, southwest China. 7 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 1 records from A revision of the genus Rhinotorus Förster, 1869 (Hymenoptera, Ichneumonidae, Ctenopelmatinae), with descriptions of three new species and an illustrated identification key. 4 records from Pycnogonidea specimens of Kuroshio Biological Research Foundation. 2 records from Two new Opadometa species (Araneae: Tetragnathidae) from Sarawak, Malaysia. 15 records from Discontinuous color variation in the assassin bug species Tiarodes miyamotoi (Hemiptera: Reduviidae: Reduviinae). 8 records from The discovery of Lepidocyrtoides Schött, 1917 (Collembola, Entomobryidae, Entomobryinae) from the New World, including three new species from Brazil and one from Australia. 1 records from Mites of the family Parasitidae Oudemans, 1901 (Acari: Mesostigmata) from Japan: a new species of Vulgarogamasus Tichomirov, 1969, and a key to Japanese species. 5582 records from Riqueza de especies y biodiversidad edáfica de una zona de humedales del Parque Nacional Arrecife de Puerto Morelos, Quintana Roo, México. 32 records from Swiss Occurrence Records of Native Species of Various Faunal Groups. 13 records from Cestode parasites (Neodermata, Platyhelminthes) from Malaysian birds, with description of five new species. 1045 records from Collection Trichoptera - SMF. 17 records from The genus Stenoterommata Holmberg, 1881 (Araneae, Pycnothelidae) in the Cerrado and Atlantic Forest from Southeastern and Central Brazil: description of four new species. 11 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 131 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 1 records from Geographically structured genetic variation in Ptychozoon lionotum (Squamata: Gekkonidae) and a new species from an isolated volcano in Myanmar. 27 records from Studies of Ptiliidae (Coleoptera) in the Spirit Collection of the Natural History Museum, London, 6: New species and records collected by W. C. Block in Kenya and Uganda, 1964 - 1965. 10384 records from CSIC-Real Jardín Botánico-Colección de Líquenes (MA-Lichen). 5 records from Campodeidae (Hexapoda: Diplura) from Kyrgyzstan, Central Asia, with the description of a remarkable new genus and species. 4 records from Cast netting new species: Integrative taxonomy of Distichodus notospilus (Characiformes: Distichodontidae) discovers new species and overlooked areas of endemism in Central Africa. 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 21 records from Brown algae specimens of Komatsu City Museum. 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 3 records from A new species, a new combination, and a new record of Crossotarsus Chapuis, 1865 (Coleoptera, Curculionidae, Platypodinae) from China. 1 records from Ecological Guild Evolution and the Discovery of the World’s Smallest Vertebrate. 14 records from Revision of the subgenus Stigmatophorella of Chalcophorella (Coleoptera: Buprestidae: Chrysochroinae). 13 records from Partial revision of the genus Robinsonia Grote 1866: description of five new species for the Neotropical fauna (Lepidoptera, Erebidae, Arctiinae, Phaegopterina). 12 records from A new species of Hypostomus Lacépède, 1803 (Siluriformes: Loricariidae) from the rio Tocantins-Araguaia basin, Brazil. 5 records from Taxonomic review of the plant bug subfamily Isometopinae for Taiwan and Japanese Southwest Islands, with descriptions of new taxa (Hemiptera: Heteroptera: Miridae: Isometopinae). 436 records from Computarización de la Colección de Referencia de Nemátodos Fitopatógenos del Centro Nacional de Referencia Fitosanitaria de la Dirección General de Sanidad Vegetal. 12 records from P. W. Lund collection in the National History Museum of Denmark, Copenhagen. 6 records from Contribution to the Mesochorinae (Hymenoptera, Ichneumonidae) of Nepal. 1145 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 497 records from KULPOL Herbarium: Tula Oblast collections of vascular plants. 43 records from A synopsis of the Family Cordagalmatidae fam. nov. (Cnidaria, Siphonophora, Physonectae). 14 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 21525 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN Fase 4 (Anfibios y reptiles). 5 records from Two new species of the genus Narcotica Sugi, 1982 (Lepidoptera: Noctuidae: Acronictinae). 649 records from Beetles from nature reserves and nearby forests in Østmarka. 885 records from CeDoc de Biodiversitat Vegetal: BCN-Seeds. 3 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera Oecophoridae) V. The unistriatella species group, with descriptions of seven new species. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 370 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 1593 records from The Broward College Insect Collection. 5 records from Systematic Notes On Kiotina Klapálek And Hemacroneuria Enderlein (Plecoptera: Perlidae), With Description Of Four New Species. 1 records from Scolopocryptops longipes sp. nov., a troglobitic scolopocryptopine centipede (Chilopoda: Scolopendromorpha: Scolopocryptopidae) from China. 1 records from Discovery of Lymantini weevils (Coleoptera: Curculionidae: Molytinae) outside the Americas: Devernodes, a new genus for five new species from Southeast Asia. 14 records from Berea College, Ralph L. Thompson Herbarium. 31 records from Macrohongos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 2 records from A new species of the Gekko japonicus group (Squamata: Gekkonidae) from Khammouane Province, central Laos. 1 records from A contribution to the knowledge of the subfamily Panagaeinae Hope, 1838 from Africa. Part 3. Revision of the Craspedophorus strachani and C. brevicollis groups (Coleoptera: Carabidae). 1 records from Glyptotermes chiraharitae n. sp., a new dampwood termite species (Isoptera: Kalotermitidae) from India. 41 records from NEON Biorepository Zooplankton Collection (DNA Extracts). 1 records from Mallomonas voloshkoae sp. nov. (Synurales, Chrysophyceae) and distribution of M. pechlaneri in mountain lakes of Siberia. 11 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 51239 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 24 records from Systematics and natural history of Southeast Asian Rock Geckos (genus Cnemaspis Strauch, 1887) with descriptions of eight new species from Malaysia, Thailand, and Indonesia. 2 records from Transfer of two South American ant species from Tapinoma Foerster 1850 to Forelius Emery 1888 (Hymenoptera: Formicidae: Dolichoderinae). 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 2 records from First record of the genus Microtityus Kjellesvig-Waering, 1966, from Puerto Rico, with description of two new species (Scorpiones: Buthidae). 1 records from Gastrodia madagascariensis (Gastrodieae, Orchidaceae): from an historical designation to a description of a new species from Madagascar. 2944 records from Weber State University Herbarium. 21 records from Description of Bagarius vegrandis, a new species of sisorid catfish from Indochina (Actinopterygii: Siluriformes), with notes on the identity of Bagarius bagarius. 4 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 3 records from Survey of sand flies (Diptera: Psychodidae: Phlebotominae) in Guajará-Mirim State Park forest reserve, near the Brazil-Bolivian border, with a description of Pintomyia fiocruzi, a new sand fly species. 509 records from Molecular phylogeny of the genus Lasiopogon (Diptera: Asilidae) and a taxonomic revision of the bivittatus section. 1 records from Taxonomic re-evaluation of the monotypic genus Pararhabdophis Bourret, 1934 (Squamata: Colubridae: Natricinae) with discovery of its type species, P. chapaensis, from China. 416 records from Colección Herpetológica-Museo de Historia Natural Unillanos. 6 records from Bees of the family Halictidae Thomson, 1869 from Dominica, Lesser Antilles (Hymenoptera: Apoidea). 59 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 3 records from A new species of Gymnophthalmus (Squamata: Gymnophthalmidae) from sand dunes of the Llanos of Apure, Venezuela. 2 records from A new species of crown-antlered deer Stephanocemas (Artiodactyla, Cervidae) from the middle Miocene of Qaidam Basin, northern Tibetan Plateau, China, and a preliminary evaluation of its phylogeny. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 28 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 1321 records from Sistematización de la colección de peces del centro de México. 100 records from Systematics, biogeography and host-plant relationships of the Neotropical jumping plant-louse genus Russelliana (Hemiptera: Psylloidea). 49063 records from UCLA Donald R. Dickey Bird and Mammal Collection. 1140 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 73 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 8 records from Two new species and a key to the dustywings of Mexico (Neuroptera, Coniopterygidae). 1 records from New Species Of The Genus Oronoqua Fennah (Hemiptera: Auchenorrhyncha: Fulgoroidea: Issidae) From Inland Ecuador. 3 records from Review of the New World Notomicrus Sharp (Coleoptera, Noteridae) I: Circumscription of species groups and review of the josiahi group with description of a new species from Brazil. 1 records from Further revision of the genus Bythotrephes Leydig (Crustacea: Cladocera: Onychopoda): redescription of B. brevimanus Lilljeborg, reevaluation of B. cederströmii Schödler, and description of a new species of the genus. 2216 records from University of Vermont, Pringle Herbarium, Algae Collection. 19 records from The Onthophagus fuscus (Coleoptera: Scarabaeidae) species complex: an update and the description of a new species. 1955 records from SIM-Fungal records compiled by Joan Montón. 6077 records from Plant specimens of Obihiro Centennial City Museum. 156052 records from Western Australian Museum provider for OZCAM. 15 records from Revision of the euryglossiform species of the Afrotropical bee genus Scrapter Lepeletier & Serville, 1828 (Hymenoptera: Apoidea: Colletidae). 3934 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 1 records from Two new Mesenchytraeus species (Annelida: Clitellata: Enchytraeidae) from Changbai Mountain, China. 1 records from The Phalacridae (Coleoptera, Cucujoidea) of Canada: new records, distribution, and bionomics with a particular focus on the Atlantic Canadian fauna. 442 records from Colección de mamíferos voladores y no voladores de la Universidad de Nariño. 1 records from On the taxonomy of Negeta semialba Hampson, 1918 with descriptions of two new Leucobaeta László, Ronkay & Witt, 2010 species (Lepidoptera, Nolidae, Nolinae). 1 records from Description of a new species of the Melanorivulus pictus species-group (Cyprinodontiformes: Rivulidae) from the Rio Paraná basin in Brazil. 2 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 7 records from Two New Species of Composetia (Annelida: Nereididae) from Small Estuaries in the Ryukyu Islands, Southern Japan, with a List of All Species Currently Belonging to Composetia. 9 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 105 records from Colección de Entomología del Museo de Historia Natural C.J. Marinkelle. 11 records from Virotia azurea (Proteaceae: Macadamieae), a striking new species endemic to New Caledonia and notes on V. francii and V. leptophylla. 1 records from Taxonomic novelties in Apocynaceae subfam. Asclepiadoideae from New Caledonia. 812 records from CEPEC herbarium - Centro de Pesquisas do Cacau - Herbário Virtual REFLORA. 1 records from A clarification of B. C. Seeman’s Malagasy species of Colea Meisn. (Bignoniaceae). 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 1 records from Clearing up Vietnamosasa (Poaceae, Bambusoideae): typification and nomenclature of a distinctive paleotropical bamboo genus. 23 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 3150 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 37 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 1666 records from SMDB - Santa Maria Departamento de Biologia. 140 records from Naturalis Biodiversity Center (NL) - Diptera. 4 records from The genus Thoradonta in Thailand (Orthoptera: Tetrigidae: Scelimeninae) with description of two new species. 1 records from A new Dysdera species (Araneae: Dysderidae) from Azerbaijan. 2 records from New species of Myrmicine ants from Western Australia (Hymenoptera: Formicidae). 13 records from Species of the genus Otacilia from Hainan Island, China (Araneae: Phrurolithidae). 3 records from Review of the enigmatic genus Boalda with transfer of pulcherrima Köhler from Nephelistis and description of two new species (Lepidoptera: Noctuidae). 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 13969 records from Flora of the Korean Peninsula. 11 records from The Stonefly Genus Lednia In North America (Plecoptera: Nemouridae). 9 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 11 records from New species of the genus Aztecatopse Haenni & Huerta from Mexico (Diptera, Scatopsidae). 17 records from Plant-parasitic nematodes of Republic of Karelia. 203 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 4 records from Pseudonemesia tabiskey, a new species of Pseudonemesia Caporiacco 1955 and new ultramorphological data for the Microstigmatinae (Araneae: Microstigmatidae). 1 records from A new species of the mud shrimp genus Axianassa Schmitt, 1924 (Decapoda: Gebiidea: Laomediidae) from the Ryukyu Islands, southern Japan. 1 records from First record to Brazil of one genera and seven species of Psychodidae (Diptera) with further new records for 10 countries on the Neotropics. 1 records from Description of a new species of Neocordulia Selys, 1882 (Odonata: Libellulidae, Corduliinae) from southern Brazil. 3 records from Channa aurantipectoralis, a new species of snakehead from Mizoram, north-eastern India (Teleostei: Channidae). 144551 records from Arizona State University Hasbrouck Insect Collection. 1 records from From an old sound recording to a new species in the genus Horatosphaga (Orthoptera: Tettigonioidea: Phaneropterinae: Acrometopini). 6 records from Taxonomic review of Dendrophryniscus brevipollicatus Jiménez de la Espada, 1870, with revalidation of D. imitator (Miranda-Ribeiro, 1920) and D. lauroi Miranda-Ribeiro, 1926, and description of four new related species (Anura, Bufonidae). 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 40171 records from Flora of the Korean Peninsula Phase II. 2 records from New species of Pycnogonum (Pycnogonida: Pycnogonidae) from Green Island Taiwan, with an additional note on the holotype of P. spatium. 3352 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 1015 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 35 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 8 records from Taxonomic revision of the genus Hirotophora Brown et al. (Diptera: Phoridae) with the description of a new species from Chile. 1 records from A new species and a new record of genus Hexacentrus Serville, 1831 (Orthoptera: Tettigoniidae: Hexacentrinae) from India. 1369 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 4 records from Two new remarkable genera and two new species of Gyponini (Hemiptera: Cicadellidae: Iassinae) from Brazil. 2274 records from Lista florística de la Costa Grande del estado de Guerrero. 1 records from Description of two new and two known species of the Genus Tylencholaimellus Cobb in M. V. Cobb, 1915 (Nematoda: Dorylaimida: Tylencholaimoidea). 346 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 177 records from Review of the Spirobolida on Madagascar, with descriptions of twelve new genera, including three genera of ' fire millipedes' (Diplopoda). 143 records from R-Bryophyta - Herbário do Museu Nacional - Bryophyta. 1 records from A new species of genus Oxytauchira from India (Orthoptera: Acrididae). 2 records from Two new charismatic Pristimantis species (Anura: Craugastoridae) from the tepuis of “ The Lost World ” (Pantepui region, South America). 46056 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 36 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 39 records from A New Species Of Isoperla Banks (Plecoptera: Perlodidae) From The Southern Appalachians, With Notes On The I. Montana Group. 6 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 2 records from Bridging the distributional gap of Tylorida striata (Thorell, 1877) and new synonymy (Araneae: Tetragnathidae). 1 records from West Palaearctic species of the genus Diostracus Loew, 1861 (Diptera: Dolichopodidae). 1 records from Revision of the Agrilus purpurifrons species-group (Coleoptera, Buprestidae, Agrilinae). 370 records from The Araneae collection (AR) of the Muséum national d'Histoire naturelle (MNHN - Paris). 21 records from Vom Wert alter Amateursammlungen - vier Spinnenarten neu für die Schweiz in der Sammlung Ketterer. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 45 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 6 records from Neoplecostomus canastra, a new catfish (Teleostei: Siluriformes) species from upper Rio Paraná basin. 15 records from New And Interesting Records Of Plecoptera (Insecta) From Slovakia And Several Autecology Notes. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 2 records from New species and new records of predaceous midges in the genera, Schizonyxhelea Clastrier and Stilobezzia Kieffer from Mexico (Diptera: Ceratopogonidae). 2 records from Neotype designation for Rhinogobius carpenteri Seale 1910, and its placement in Tukugobius Herre 1927 (Teleostei: Gobiidae). 41 records from Transfer of the Malagasy genera Humbertianthus and Macrostelia to Hibiscus (Malvaceae) with description of four new species. 4 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 90 records from The genus Leptostylopsis of Hispaniola (Coleoptera, Cerambycidae, Acanthocinini). 145 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 3 records from A new species of the genus Larsia Fittkau (Diptera: Chironomidae) from India with cladistic analysis and a world key to the known males. 14498 records from Propuesta de actualización del Catálogo de Autoridades Taxonómicas (CAT) de Lepidoptera: Heterócera para la Península de Yucatán. 3 records from New Species of Blindsnakes (Squamata: Gerrhopilidae) from the offshore islands of Papua New Guinea. 1 records from New species of Heteropathes (Anthozoa: Antipatharia) expands genus distribution to the NE Atlantic. 4 records from Two new genera of Oriental xyleborine ambrosia beetles (Coleoptera, Curculionidae: Scolytinae). 12 records from A new species of Pimelodella Eigenmann & Eigenmann, 1888 (Siluriformes: Heptapteridae) from the Orinoco River basin. 935 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 2 records from A revision of the Chilean Brachyglutini - Part 4. Revision of Achilia Reitter, 1890: A. puncticeps and A. approximans species groups, with description of seven new species (Coleoptera: Staphylinidae: Pselaphinae). 4 records from Pseudofeltria (Acariformes: Pionidae) In Europe: Three Previously Described Taxa, A Species New To Science From The Northern Apennines, And A Redefinition Of Foreliinae. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 13 records from New species of Tingidae (Insecta: Heteroptera) from Madagascar. 3 records from Four new species and new records of Atopsyche Banks (Trichoptera: Hydrobiosidae) from Pantepui biogeographical region (Venezuela). 79 records from Marine algal (seaweed) flora of São Jorge Island, Azores. 5 records from A northern range extension of a Canadian species of Special Concern, Dielis pilipes (Hymenoptera: Scoliidae), in the Okanagan Valley of British Columbia. 4 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 266099 records from Vascular Plant Specimen database of Kanagawa Prefectural Museum of Natural History. 1 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 2 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 4 records from Two new species of the genus Deltomerodes Deuve, 1992 (Coleoptera, Carabidae, Patrobini) from Xizang, China. 29263 records from Herbarium Horti Botanici Pisani (PI), Sistema Museale di Ateneo, Università di Pisa. 19 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 11 records from A review of the Asian orb weaving spider genus Pronoides (Araneae: Araneidae). 30 records from Molecular study supports the position of the New Zealand endemic genus Lamellomorpha in the family Vulcanellidae (Porifera, Demospongiae, Tetractinellida), with the description of three new species. 2 records from Pseudanthias emma new species, with notes on a collection of anthiadine serranid fishes from off Myanmar (eastern Indian Ocean). 7822 records from Bryophytes specimens of Akita Prefectural Museum. 5 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 3 records from Revisión del género Microogenius Gutiérrez (Coleoptera: Scarabaeidae: Rutelinae: Rutelini), con descripción de dos nuevas especies altoandinas. 45646 records from Field Museum of Natural History (Botany) Pteridophyte Collection. 2533 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 11935 records from Hatikka.fi observations. 1 records from The First Record of a Species of Clausiidae (Copepoda: Cyclopoida) from Japanese Waters, with the Proposal of a New Genus. 24 records from Taxonomy of the genus Autosticha Meyrick (Lepidoptera: Autostichidae) in China Descriptions of fifteen new species. 2189 records from CAS Entomology Type (TYPE). 2 records from Report of a new genus Mirigryllus belonging to tribe Modicogryllini, with a new species M. nigrus from Zhejiang, China (Orthoptera: Gryllidae: Gryllinae Modicogryllini). 14 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 4 records from A new species of the genus Urumaelmis Satô (Coleoptera, Elmidae, Macronychini) from Kyushu Island, Japan. 5 records from Five new species of the genus Primulina (Gesneriaceae) from Limestone Areas of Guangxi Zhuangzu Autonomous Region, China. 243 records from Sponges of the Guyana Shelf. 2246 records from Base de datos de la Colección zoológica del Instituto de Investigación de zonas desérticas de la Universidad Autónoma de San Luis Potosí (BDCZIID-UASLP). 10853 records from MBML-Anfibios - Coleção de Anfíbios MBML. 119 records from Kinorhyncha. 1 records from Mycomystes nigriventris sp. nov. (Coleoptera: Erotylidae: Tritomini) from South America, with insights into the genus Mycomystes Gorham. 1449 records from Dataset of herbarium specimens of threatened vascular plants in Catalonia. 3 records from Notes on the genus Echinops L. (Asteraceae) in SE Europe. 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 3 records from The Oncometopia orbona species group (Hemiptera, Cicadellidae, Proconiini). 2 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 581 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 11370 records from CHAS Ornithology (Arctos). 4 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 129 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 4 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 1771 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 5 records from Three new species of Eusarcus Perty, 1833 (Opiliones, Gonyleptidae) from Brazilian caves. 1 records from Mycetocharina (Alleculopsis) bahukalatensis sp. nov. (Coleoptera: Tenebrionidae: Alleculinae) from Iran. 3 records from Parochodaeus bituberculatus (Erichson) (Coleoptera: Ochodaeidae) and Faargia gentilii (Martínez) (Coleoptera: Scarabaeidae), two species newly discovered in Chile. 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 3 records from Description of two new species of ants of the genus Myrmecina Curtis, 1829 (Hymenoptera: Formicidae: Myrmicinae) from the Eastern Himalayas. 169 records from Barcant Butterfly Collection - Papilionidae. 1297 records from Biodiversidad de productores primarios de las lagunas costeras del norte de Yucatán. 2 records from New data of Nazeris Fauvel in Xizang, China (Coleoptera, Staphylinidae, Paederinae). 1 records from Taxonomic updates for some confusing Micronesian species of Camponotus (Hymenoptera: Formicidae: Formicinae). 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 1 records from A new species of Psammophis (Serpentes: Psammophiidae) from the Turpan Basin in northwest China. 3 records from Two new species and key to the salina group of the genus Rhagovelia Mayr, 1865 (Hemiptera: Heteroptera: Veliidae) from Colombia. 10075 records from Nematoda of Costa Rica (INBio). 4 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 1 records from A new Puddle Frog, genus Phrynobatrachus (Amphibia: Anura: Phrynobatrachidae), from the eastern part of the Upper Guinea biodiversity hotspot, West Africa. 4 records from Description of four new species of the Cirolana ‘ parva group’ (Crustacea: Isopoda: Cirolanidae) from Thailand, with supporting molecular (COI) data. 6 records from Revision of the family Acidopsidae Števčić, 2005, and the systematic position of Typhlocarcinodes Alcock, 1900, Caecopilumnus Borradaile, 1902, and Raoulia Ng, 1987, with descriptions of two new genera and five new species (Crustacea: Brachyura: Goneplacoidea). 274 records from Crabs from Vietnam and Indonesia. 5 records from Three new species of the Stenus cephalotes group fom Zhejiang, East China (Coleoptera, Staphylinidae). 157 records from West African pholcid spiders: an overview, with descriptions of five new species (Araneae, Pholcidae). 1 records from A new species of Dicrotendipes (Diptera: Chironomidae) from Florida. 2 records from The genus Cylloepus Erichson, 1847 (Coleoptera: Elmidae: Elminae) new species and combinations. 4 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 8812 records from IAN herbarium - Embrapa Amazônia Oriental - Herbário Virtual REFLORA. 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 2451 records from Macrobenthos Chukchi Sea, 1986. 1561 records from Colección de hongos del Herbario "Jaime Andrés Rodríguez". LEB-Fungi. 35 records from Taxonomic revision of the Neotropical genus Ormiophasia Townsend, 1919 (Diptera: Tachinidae), with the description of eight new species. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 1 records from A new diploid species belonging to the Odontophrynus americanus species group (Anura: Odontophrynidae) from the Espinhaço range, Brazil. 8 records from Distribution And New Records Of Lymexylidae (Coleoptera: Lymexyloidea) In Guatemala And Mexico. 586 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 516 records from Herbarium of the Institute of the problems of Northern development (TMN). 3827 records from UTEP Invertebrates (Arctos). 6 records from Notes on the first instar larvae of the genus Tipula (Diptera: Tipulidae). 3 records from Taxonomy of the Myrmicine ant genus Temnothorax Mayr, 1861 (Formicidae: Myrmicinae) in the Arabian Peninsula. 1798 records from Mammals in MZNA-VERT: project Human impacts in rivers of Navarra. 15 records from Fish occurrence in Kuban River basin. 4 records from Revision of the Traumatomutilla gemella species-group (Hymenoptera, Mutillidae) with the description of its hitherto unknown males. 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 4 records from A new skink of the genus Scincella Mittleman, 1950 (Squamata: Scincidae) from Ba Den Mountain, Tay Ninh Province, southern Vietnam. 10 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 4 records from Four new species of terrestrial-breeding frogs of the genus Phrynopus (Anura: Terrarana: Craugastoridae) from Río Abiseo National Park, Peru. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 23481 records from AMNH Bird Collection. 6 records from New species of Phaloria (Orthoptera: Phalangopsidae: Phaloriinae) from West Papua (Indonesia). 4 records from Revision of Chaetacanthus Seidler, 1922 (Annelida, Phyllodocida, Polynoidae). 658 records from Flora útil del Municipio de la Huerta, Jalisco. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 57 records from Seven new giant pill-millipede species and numerous new records of the genus Zoosphaerium from Madagascar (Diplopoda, Sphaerotheriida, Arthrosphaeridae). 1146 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 4 records from Psychotria niauensis sp. nov. (Rubiaceae), espèce calcicole endémique de la Polynésie française, décrite de l’atoll soulevé de Niau (Tuamotu). 2 records from A new diurnal gecko in the genus Gonatodes (Squamata: Sphaerodactylidae) from the foothills of the Serranía de San Lucas, Norosí-Colombia. 21 records from Taxonomic revision of Ceropegia sect. Huernia (Asclepiadoideae, Apocynaceae) in Saudi Arabia with three new combinations. 20 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 2 records from Re-description of Orchestia stephenseni Cecchini, 1928: designation of neotype and senior synonym to Orchestia constricta A. Costa, 1853 (Crustacea: Amphipoda: Talitridae) by Reversal of Precedence. 5 records from Thunberga gen. nov., a new genus of huntsman spiders from Madagascar (Araneae: Sparassidae: Heteropodinae). 4 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 4 records from Review of the genus Holostaspis Kolenati, 1858 (Acari: Laelapidae). 7 records from Revision of the Agrilus gratiosus species-group (Coleoptera, Buprestidae, Agrilinae). 47 records from Asturodes Amsel (Lepidoptera: Crambidae: Spilomelinae): Three New Species From The Western Hemisphere And Food Plant Records From Area De Conservación Guanacaste, Costa Rica. 13 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 4 records from Bemerkenswerte Faltenwespen aus der äthiopischen Region. Teil 14 (Hymenoptera, Vespidae, Eumeninae). 4 records from Revision of the species related to Lalagetes subfasciatus Boheman and transfer of remaining Lalagetes species to other genera of Embrithini (Coleoptera: Curculionidae: Entiminae). 4123 records from Bryological collection of Yugra State University. 2 records from Review of subterranean Quedius, with description of the first hypogean species from the Russian Far East (Coleoptera: Staphylinidae: Staphylinini). 1654 records from Naturalis Biodiversity Center (NL) - Crustacea. 215 records from Propuesta de diagnóstico, erradicación y monitoreo post-erradicación, de especies exóticas invasoras en oasis de Baja California Sur, centrándose en las dos más relevantes: rana toro Lithobates catesbeianus y manto de cristo Cryptostegia grandiflora. 3 records from Epiproct And Dorsal Process Structure In The Allocapnia Forbesi Frison, A. Pygmaea (Burmeister), And A. Rickeri Frison Species Groups (Plecoptera: Capniidae), And Inclusion Of A. Minima (Newport) In A New Species Group. 2 records from On the identity of the Palearctic species of the wolf spider genus Trebacosa (Araneae: Lycosidae). 2 records from Revision of the ant genus Anillomyrma Emery, 1913 (Hymenoptera: Formicidae: Myrmicinae: Solenopsidini).. 3 records from A new Synbranchus (Teleostei: Synbranchiformes: Synbranchidae) from ilha de Marajó, Pará, Brazil, with notes on its reproductive biology and larval development. 1 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 11 records from New insights into polyphyly of the harpacticoid genus Delavalia (Crustacea, Copepoda) through morphological and molecular study of an unprecedented diversity of sympatric species in a small South Korean bay. 1 records from A new, enigmatic species of black-eyed gecko (Reptilia: Diplodactylidae Mokopirirakau) from North Otago, New Zealand. 1 records from A new crayfish of the genus Cambarus Erichson, 1846 (Decapoda: Cambaridae) from an under-sampled habitat type in central Ten- nessee, USA. 7599 records from ERBG AVH data. 69 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 49986 records from Tiroler Landesmuseum Ferdinandeum. 3 records from Seven species of Pseudopecoeloides Yamaguti, 1940 (Digenea, Opecoelidae) from temperate marine fishes of Australia, including five new species. 87 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 1090 records from Colección de Mamíferos del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-M). 854 records from Análisis de Integridad Biológica en la Reserva Forestal Protectora Regional Bitaco. Convenio CVC- Univalle 108 de 2017. 450 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009 (Chihuahua). 1 records from Hydaticus (Prodaticus) hauthi sp. nov., a new diving beetle from the cloud forest in the Cordillera El Sira, Peru (Coleoptera: Dytiscidae). 4148 records from WII Herbarium Dataset. 1802 records from Diatomeas bentónicas de los oasis de Baja California Sur. 24053 records from Quaid-i-Azam University Herbarium. 7 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 1 records from Bryozoans Specimens of Akita Prefectural Museum. 2 records from Two new species of the genus Malayepipona Giordani Soika (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with updated key to all recognised species. 6 records from Two new Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from the Shevaroy massif, Tamil Nadu, India, with a preliminary ND 2 phylogeny of Indian Cnemaspis. 2 records from A new species of cascade frog (Amphibia: Ranidae) in the Amolops monticola group from China. 64 records from Carrion beetles (Coleoptera, Silphidae) of Volga-Kama Nature Reserve. 12 records from Gamasiphis species (Acari: Mesostigmata: Ologamasidae) from Ecuador, with description of a new species and new records. 6 records from Two new species and records of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae) from southeastern China. 1677 records from Structures and Nutrition Requirements of Macrozoobenthic Communities in the area of the Lomonossov Ridge, 1995-1998. 1 records from Thraulodes marianoi sp. nov., a remarkable new species of mayfly (Ephemeroptera Leptophlebiidae) with dark wings from the southern Brazilian Atlantic Forest. 3 records from Some new species of Phaneroptera, Eulioptera and Scolocerca (Orthoptera Tettigoniidae: Phaneropterinae) from West Tropical Africa. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 2 records from Description of Lacon mertliki sp. nov. (Coleoptera: Elateridae: Agrypninae) from the Hyrcanian forest ecoregion, with a key to the Lacon species of Iran. 1 records from Tibetyrus gen. nov., a new myrmecophilous Tyrini from Xizang, China (Coleoptera: Staphylinidae: Pselaphinae). 2 records from A new species of Nigrobaetis Novikova & Kluge, 1987 (Ephemeroptera, Baetidae) from Tamil Nadu, India. 5 records from Description of two new species of Magnispina and a new hypothesis of phylogenetic relationships for Heteropachylinae (Opiliones: Laniatores: Gonyleptidae). 5 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 13 records from Species of Prioninae, Parandrinae, Lepturinae (Insecta, Coleoptera, Cerambycidae) and Disteniidae (Insecta, Coleoptera) from east Paraná State (Brazil), with three new geographic distribution records. 286 records from California State University, Long Beach Birds. 1479 records from Epiphytic mosses from the northwest Iberian quadrant (Spain). 438 records from Specimen references on the Rubiaceae family held by theTAN Herbarium. 4 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 221 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 31 records from A New Species Of Apostenus From California, With Notes On The Genus (Araneae, Liocranidae). 1 records from A new species and a key to world species of the flavipes species-group of the genus Cotesia Cameron, 1891 (Hymenoptera: Braconidae: Microgastrinae) from Japan. 18 records from Mammals in MZNA-VERT: project Loza. 5 records from Description of eight new species of the traumatically inseminating plant bug genus Coridromius (Heteroptera: Miridae: Orthotylinae: Coridromini). 4 records from Two new species in the Russula (Russulaceae, Basidiomycota) crown clade from Indian Himalaya. 8 records from Review of the genus Valdasus Stål, 1860 (Heteroptera, Miridae, Cylapinae), with descriptions of four new species from Brazil, Ecuador and French Guiana. 2 records from A new catfish species of the genus Trichomycterus (Siluriformes: Trichomycteridae) from the río Orinoco versant of Páramo de Cruz Verde, Eastern Cordillera of Colombia. 568 records from Philippine Mollusk Symbiont - ICBG Collection. 5 records from Sonerila konkanensis (Melastomataceae), a new species from South Goa, India. 1 records from New species of the snakefly genus Mongoloraphidia (Raphidioptera: Raphidiidae) from China. 12 records from Review of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) of Iran and adjacent territories. 7446 records from BioGIS - Vascular plants - Israeli Gene Bank. 13 records from Taxonomic study of the genus Promalactis Meyrick (Lepidoptera, Oecophoridae) from Hainan Island, China (III). 612 records from Distribución, estructura poblacional y variación genética de algunas especies de pinos en peligro de extinción en México. 10 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 4 records from Review the bamboo-feeding genus Arcofaciella Fennah, 1956 (Hemiptera: Fulgoromorpha: Delphacidae) with description of a new species from India. 52 records from New species of Cirratulidae (Annelida, Polychaeta) from abyssal depths of the Clarion-Clipperton Fracture Zone, North Equatorial Pacific Ocean. 1 records from An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia. 6000 records from University of Cincinnati, Margaret H. Fulford Herbarium - Lichens. 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 2650 records from E. C. Smith Herbarium (ACAD) - Cape Breton University Collection. 1 records from Acantorna-a new genus of Hymedesmiidae (Porifera, Demospongiae Poecilosclerida) from the western Aleutian Islands of Alaska with description of Acantorna tahoma n. sp.. 3 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 2 records from A new species of rheophilic cyprinid fish (Teleostei: Cyprinidae) from the Brahmaputra Basin, northeast India. 10 records from Mammalians Specimens of Akita Prefectural Museum. 2 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 7956 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 1 records from Description of a new Oriental stonefly species, Phanoperla constanspina (Plecoptera: Perlidae) from Mindanao, Philippines and association of life stages using DNA barcoding. 2 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 6250 records from Los mamíferos del estado de Durango, México. 91 records from Vascular plants occurrences in Dokdo islands, Korea, based on herbarium collections and legacy botanical literature. 7 records from New species of Xiphoniscus and new record of Androdeloscia escalonai (Isopoda, Scutocoxifera, Oniscidea, Philosciidae) from Brazilian Amazon. 136 records from Occurrence data of some marine invertebrates and freshwater crabs housed in the natural history collection at the National Museums of Kenya. 3 records from ALLIUM (AMARYLLIDACEAE) SPECIES IN PAKISTAN: TWO NEW RECORDS AND A NEW SPECIES FROM ZHOB (BALOCHISTAN). 106867 records from MSB Fish Collection (Arctos). 1 records from A contribution to the taxonomy of Anthaxia (Cratomerus) (Coleoptera Buprestidae: Anthaxiini) of East Africa. 1 records from A New Species of Abbrosoga (Hemiptera: Fulgoroidea: Delphacidae), An Endemic Puerto Rican Planthopper Genus, with an Updated Checklist of the Delphacidae of Puerto Rico. 2 records from The first species of the pseudoscorpion genus Lechytia Balzan, 1892 (Pseudoscorpiones, Chthoniidae) from New Zealand. 1 records from Minute but constant morphological differences within members of Stenothoidae: the Stenothoe gallensis group with four new members, keys to Stenothoe worldwide, a new species of Parametopa and Sudanea n. gen. (Crustacea: Amphipoda). 1 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 11 records from The genus Ophiogomphus Lieftinck, 1964 in Vietnam, with descriptions of the female of O. minimus Karube, 2014 and O. phantoani sp. nov. (Odonata: Gomphidae). 59 records from Biodiversity of the scentless plant bugs (Hemiptera: Rhopalidae) in southern South America. 610 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 18 records from Glasgow Museums Biological Records Centre: Coleoptera: Byyrhidae, Clambidae, Dascillidae & Phalacridae. 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 3 records from New species of oribatid mites of the family Oppiidae (Acari, Oribatida) from Chile. 1 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 25 records from Four new species of Psychomyia (Trichoptera: Psychomyiidae) from China, with re-descriptions of two species. 3 records from Two new species of the genus Tylostega Meyrick, 1894 (Lepidoptera: Crambidae) from China, with a list of all the known species in the world. 10 records from The Trichoptera of Panama XIII. Further new country records for caddisflies (Insecta: Trichoptera) from the Republic of Panama. 5 records from The species of the bee genus Centris of the “ hyptidis group ” revisited with the description of Centris (Anisoctenodes) new subgenus (Hymenoptera: Apidae: Centridini). 1 records from Description of a new species of Megischus Brulle (Hymenoptera, Stephanidae), with a key to the species from China. 3 records from A new species of Caenis Stephens, 1835 (Ephemeroptera: Caenidae) from Tamil Nadu, Southern India. 370 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 7215 records from VIT Herbarium - Mycotheca (The Natural History Museum of Álava). 8 records from Vermont Orthoptera Records from Historic Dot Maps. 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 12 records from A new species and new records of Oocyclus Sharp, 1882 (Coleoptera: Hydrophilidae) from Brazil. 3 records from Integrative taxonomy of Thalerosphyrus Eatonı 1881 (Ephemeropteraı Heptageniidae) in Thailand. 3927 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 2 records from The pseudoscorpion genus Verrucachernes (Pseudoscorpiones: Chernetidae) in the Indian region. 1 records from Timea bioxyasterina sp. n., a new species from the Northeastern coast of Brazil (Demospongiae, Hadromerida). 1 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 2 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 6407 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 2 records from Moenkhausia restricta, a new species from the upper Rio Negro, Amazon basin, northwestern Brazil (Characiformes: Characidae). 19 records from Four new species of Paranaitis Southern, 1914 (Phyllodocidae, Annelida) from southern and southeastern Brazil. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 2 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 2 records from A new species of Hemigrammus Gill 1858 (Characiformes: Characidae) from the upper Rio Negro, Amazon basin, Brazil. 95 records from Marine algal (seaweed) flora of Faial Island, Azores. 6 records from New species of Culex (Culiciomyia) (Diptera: Culicidae) from Talangaye Forest in Cameroon and descriptions and identification keys for males of the Afrotropical species of the subgenus. 5 records from Integrative description of new giant pill-millipedes from southern Thailand (Diplopoda, Sphaerotheriida, Zephroniidae). 4 records from Description of Brachymeria philornisae sp. n. (Hymenoptera: Chalcididae), a parasitoid of the bird parasite Philornis trinitensis (Diptera: Muscidae) in Tobago, with a review of the sibling species. 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 4 records from Taxonomy of Probolodus Eigenmann, 1911 (Characiformes: Characidae) with description of two new species, and comments about the phylogenetic relationships and biogeography of the genus. 21 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 1873 records from Odonata de la huasteca potosina (insecta). 4 records from Herbarium Senckenbergianum (FR) - Protista. 6 records from Deep-sea (> 1000 m) Goniasteridae (Valvatida; Asteroidea) from the North Pacific, including an overview of Sibogaster, Bathyceramaster n. gen. and three new species. 2 records from The myth of monophagy in Paralobesia (Lepidoptera: Tortricidae)? A new species feeding on Cypripedium reginae (Orchidaceae). 31 records from Checklist of rust fungi (Pucciniales) occurring in Portugal. 3 records from Two new species of Parandrinae (Coleoptera: Cerambycidae) in the genera Parandra and Acutandra from South America. 1624 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 1 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 46 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 21 records from The Oribatid Family Phthiracaridae III. Redescription of Phthiracarus nitens (Nicolet). 1 records from Echinodera (Ruteria) soumasi sp. n. from Greece (Coleoptera, Curculionidae). 4 records from Osmiine bees of the genus Haetosmia (Megachilidae, Osmiini): biology, taxonomy and key to species. 4117 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 36 records from Ephemeroptera from the Venezuelan Guayanas´s Uplands: Families Leptophlebiidae, Euthyplociidae and Oligoneuriidae. 54 records from Descriptions of two new species of Brachyzapus Gauld & Dubois (Hymenoptera: Ichneumonidae: Pimplinae) from South Korea with key to a Palaearctic species. 677 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 4 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 114 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 10 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Echinodermata. 89 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 2 records from Mammals of the Natural Laboratory of Peat-Swamp Forest, Sebangau, Central Kalimantan, Indonesia. 195 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 171 records from Echinoderms from the Seaflower Biosphere Reserve. 1 records from Gobiesox lanceolatus, a new species of clingfish (Teleostei: Gobiesocidae) from Los Frailes submarine canyon, Gulf of California, Mexico. 2 records from A review of the genera Anasillomos Londt, 1983, Oratostylum Ricardo, 1925, and Remotomyia Londt, 1983, with description of a new genus and two new species (Diptera: Asilidae: Stenopogoninae). 4 records from Reassessment of the taxonomic status of Pseudopaludicola parnaiba (Anura, Leptodactylidae, Leiuperinae), with the description of a new cryptic species from the Brazilian Cerrado. 4 records from Two more new species of the Cyrtodactylus peguensis group (Squamata: Gekkonidae) from the fringes of the Ayeyarwady Basin, Myanmar. 5981 records from ZUEC-GAS - Coleção de Gastropoda do Museu de Zoologia da UNICAMP. 333 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 14 records from Novitates neocaledonicae IV: Three new species of Cryptocarya R. Br. (Lauraceae). 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 208069 records from South Australian Museum Australia provider for OZCAM. 76 records from New species and records of Caulleriella (Annelida, Cirratulidae) from shelf and slope depths of the Western North Atlantic Ocean. 1 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 2 records from Novelties from the Northern Mountains Complex of Madagascar IV: A new Rinorea Aubl. (Violaceae) of restricted range from the Galoko and Kalabinono massifs. 98 records from Brock University Herbarium (BU). 11 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 1 records from Description of the last stadium larva of Erythrodiplax abjecta (Anisoptera: Libellulidae) from the eastern Colombian Andes. 20 records from Review of the genus Saropogon Loew, 1847 (Diptera: Asilidae) from Russia Transcaucasia and Central Asia, with description of three new species. 203 records from Revision of the Neotropical caddisfly genus Phylloicus (Trichoptera: Calamoceratidae). 2 records from New data on the genus Syndicus Motschulsky (Coleoptera: Staphylinidae: Scydmaeninae) from Yunnan, southern China. 3 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 96 records from New species and records of deep-water Orbiniidae (Annelida, Polychaeta) from the Eastern Pacific continental slope, abyssal Pacific Ocean, and the South China Sea. 9 records from Review of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae Anthophagini) of the Iberian Peninsula. 2 records from A taxonomic revision of the Western Palaearctic genus Cacochroa Heinemann 1870 (Lepidoptera, Depressariidae, Cryptolechiinae) with description of a new genus and a new species. 10 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 10 records from The West and Central African species of Vepris Comm. ex A. Juss. (Rutaceae) with simple or unifoliolate leaves, including two new combinations. 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 3 records from Dombeya sevathianii (Malvaceae): A new critically endangered species endemic to Mauritius (Indian Ocean). 1 records from Collection Mantodea - SMF. 18 records from Monocotyledonous Geophytes of Fergana Valley. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 102 records from Swedish Malaise Trap Project (SMTP) - Evaniidae. 155 records from Taxonomic revision of the genus Prionopelta Mayr, 1866 (Formicidae: Amblyoponinae) for the Neotropical region. 36 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 77 records from UWIZM Cnidarians. 17 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 1 records from Pyrrosia sarthalensis, a new species of Polypodiaceae from Kathua District, Jammu and Kashmir, Western Himalaya, India. 10 records from Pauropoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 3 records from A new species of the spider genus Solenysa from China (Araneae, Linyphiidae). 1 records from Planothidium galaicum sp. nov. (Bacillariophyta, Achnanthidiaceae), a new diatom species from Galician coast, Spain. 299 records from Colección Taxonómica Nacional de Insectos “Luis María Murillo” (CTNI). 35741 records from Taiwan Forestry Research Institute. 33814 records from NEON Biorepository Carabid Collection (Pinned Vouchers). 78 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 92 records from A list of coleoptera recorded in Mixed Forest habitat in Arabuko-Sokoke Forest, Kenya. 140 records from Swedish Malaise Trap Project (SMTP) - Braconidae: Cheloninae: Adelius. 2 records from Two new species of Podonomus Philippi (Diptera: Chironomidae: Podonominae) from mountains of Southeastern Brazil. 1 records from First record of the freshwater crab genus Esanthelphusa Naiyanetr, 1994 (Decapoda: Brachyura: Gecarcinucidae) from Myanmar, with the description of a new species from the Kayin State. 7541 records from MHA Herbarium: Collections of mosses from Yana-Indigirka Region, Yakutia, Russia. 1 records from Ecología e historia natural de Schistocerca americana socorro y S. piceifrons piceifrons en Isla Socorro. 4005 records from Colección Taxonómica Central del Museo Entomológico UNAB, familia Melolonthidae. 35 records from Revision of the stygobiont gastropod genera Plagigeyeria Tomlin, 1930 and Travunijana Grego & Glöer, 2019 (Mollusca; Gastropoda; Moitessieriidae and Hydrobiidae) in Hercegovina and adjacent regions. 11 records from Revision of the Madagascan genera Oncodopus Brongniart and Colossopus Saussure (Orthoptera: Tettigoniidae: Conocephalinae; Euconchophorini), with description of Malagasopus gen. nov.. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 12 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 1581 records from La familia Asclepiadaceae en México. 3 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 7 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 2471 records from Colección de Rosales, Salviniales, Santalales, Sapindales, Saxifragales, Schizaeales y Selaginellales del Museo Botánico CORD - IMBIV. 70 records from Swedish Malaise Trap Project (SMTP) - Odonata. 1 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 39 records from Swedish Malaise Trap Project (SMTP) - Formicidae. 26 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 1422 records from Royal Belgian Institute of Natural Sciences Bryozoa collection. 17 records from Six new species of Otacilia from southern China (Araneae: Phrurolithidae). 5 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 15 records from Cellaria (Bryozoa, Cheilostomata) from the deep: new species from the southern Zealandian region. 14 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 5 records from Two new species of viviparous halfbeaks (Atherinomorpha: Beloniformes: Zenarchopteridae) endemic to Sulawesi Tenggara, Indonesia. 2 records from A new species of Plurellidae (Ascidiacea: Phlebobranchia) from Papua New Guinea. 14 records from Two new species of Balacha (Insecta: Hemiptera: Cicadellidae: Cicadellinae) from Brazil with comments on their phylogenetic position and biogeography. 2 records from Sinibotia lani, a new species of botiid loach (Teleostei: Botiidae) from Guangxi, China. 1407 records from Donación de la base de datos del Dr. Ortega Paczka resultados de la computarización de datos de colecta de muestras de maíz y otros cultivos asociados de diferentes regiones de México. 4 records from Confirmation of Gonioctena rufa (Kraatz, 1879) (Coleoptera: Chrysomelidae) in northeastern Asia, previously misinterpreted as a subspecies of G. viminalis (Linnaeus, 1758), and a new synonym in the genus. 20 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 38 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 76 records from Bryophyte speciments of Toyota City Nature Sanctuari (TCNS).. 1 records from First record of a living ditaxiporine catenicellid in the Atlantic, with a description of Vasignyella ovicellata n. sp. (Bryozoa). 5 records from Three new species of deep-sea Gromia (Protista, Rhizaria) from the bathyal and abyssal Weddell Sea, Antarctica. 1 records from Description of five new species of American Acanthocinini (Coleoptera, Cerambycidae, Lamiinae). 322 records from Sistemática del género Polianthes L (Agavaceae). 1889 records from Ims fish tag database. 1 records from Taxonomic revision of the genus Lycenchelys (Osteichthyes: Zoarcidae) in Japanese waters. 40 records from A new species of the grass-feeding leafhopper genus Amblysellus Sleesman (Hemiptera: Cicadellidae: Deltocephalinae) from western Mexico, with a checklist and key to species. 1 records from A new species of Pothea, with new records and taxonomic notes on other species of the genus (Hemiptera: Heteroptera: Reduviidae). 12 records from Review of the species of the genus Serrapinnus Malabarba, 1998 (Teleostei: Characidae: Cheirodontinae) from the rio Tocantins-Araguaia basin, with description of three new species. 30636 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 10 records from Spider hosts (Arachnida, Araneae) and wasp parasitoids (Insecta, Hymenoptera, Ichneumonidae, Ephialtini) matched using DNA barcodes. 2 records from Glasgow Museums BRC: Chrysomelidae. 4 records from New Species And Records Of Anacroneuria (Plecoptera: Perlidae) From Ecuador And Paraguay. 8 records from The first record of Gnathostenetroididea Kussakin, 1967 from Australian waters with description of four new species of Gnathostenetroides Amar, 1957 (Crustacea: Isopoda: Asellota) from the Great Barrier Reef. 13 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 7 records from A new genus Viperinus Park with descriptions of two new species, and two new species of the genus Protolychnis Meyrick, 1925 (Lepidoptera, Gelechioidea, Lecithoceridae) in Kenya and Tanzania, with a checklist of the world species. 876431 records from Texas A&M University Insect Collection. 214 records from Insectarium René-Martineau (IRM). 2 records from The deep-water Calappidae, Matutidae and Leucosiidae of the Solomon Islands, with a description of a new species of Euclosia Galil, 2003 (Crustacea, Decapoda, Brachyura). 81667 records from Herbarium of Shinshu University. 1 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 2782 records from USAC Mammals Collection. 209357 records from KUBI Herpetology Collection. 1 records from The uncommon Neotropical genus Pazius Navás, 1913 (Mecoptera: Bittacidae): a comprehensive synthesis, with description of a new Brazilian species. 1 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 3160 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 22 records from Review of Lepidocyrtinus Börner, 1903 (Collembola, Entomobryidae, Seirinae): the African species. 2 records from Two new species of Biantes from China and Malaysia (Opiliones: Laniatores: Biantidae). 2 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 78 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 788 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 5879 records from FLOR herbarium - Universidade Federal de Santa Catarina - Herbário Virtual REFLORA. 7 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 1173 records from Données de collection de l'inventaire des Papillons de jour de Martinique. 208 records from Anguillosyllis (Annelida: Syllidae) from multiple deep-water locations in the northern and southern hemispheres. 24 records from Revision of the enigmatic Southeast Asian spider genus Savarna (Araneae, Pholcidae). 5 records from The discovery of Rock Geckos Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) in the Tanintharyi Region, Myanmar with the description of two new species. 19 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 147 records from The genus Tarsonemus Canestrini and Fanzago, 1876 (Acari: Heterostigmatina: Tarsonemidae) in East Azerbaijan, Iran, with a description of T. lenticulatus sp. nov. and re-description of T. annotatus Livshits, Mitrofanov and Sharonov, 1979. 6 records from Four new species of Scydmaeninae and Pselaphinae (Coleoptera: Staphylinidae) from Yunnan, China. 5 records from Gergithoides Schumacher, 1915 in Vietnam, with two new species, and taxonomic notes on the genus (Hemiptera: Fulgoromorpha: Issidae). 85 records from Colección Nacional de Lombrices de Tierra Universidad Tecnológica de Pereira (CNLT UTP). 3 records from New species and records of Angolan Limnichidae (Coleoptera: Byrrhoidea). 27 records from Colección Invertebrados-Museo de Historia Natural Unillanos. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 9 records from Neue Arten der Gattung Atomaria STEPHENS, 1830 aus der Türkei und dem Irak (Coleoptera, Cryptophagidae). 36 records from A new species of the genus Watsonidia Toulgoët, 1981 (Lepidoptera, Erebidae, Arctiini): example of polymorphism in the Amazon of Peru. 29717 records from ASE herbarium - Universidade Federal de Sergipe - Herbário Virtual REFLORA. 111 records from Collection Hydrozoa - ZSM München. 3055 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from A new Dondice Marcus Er. 1958 (Gastropoda: Nudibranchia) from the Mediterranean Sea reveals interesting insights into the phylogenetic history of a group of Facelinidae taxa. 23117 records from FKSE-Herbarium of Faculty of Symbiotic Systems Science, Fukushima University, Japan. 3 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 2 records from Molecular circumscription of new species of Gyrocotyle Diesing, 1850 (Cestoda) from deep-sea chimaeriform holocephalans in the North Atlantic. 3 records from Hurleyella, a new genus of Nearctic Dolichopodidae (Diptera). 309 records from Colección de chinches (Insecta: Hemiptera) del Centro de Colecciones Biológicas de la Universidad del Magdalena. 16 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 243 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 4050 records from Estudio taxonómico distribucional de los peces del estado de Chiapas, México. 5 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 2 records from A new species of Paralithoxus (Siluriformes: Loricariidae: Ancistrini) from the highlands of Serra da Mocidade, Roraima State, Brazilian Amazon. 404 records from Antarctic and SubAntarctic Ophiuroidea - MNA (Section of Genoa). 3 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 632 records from 2019_NSMK_PL. 1 records from Тaxonomic position of Orthochirus olivaceus (Karsch, 1881), the type species of the genus Orthochirus Karsch, 1892 (Scorpiones: Buthidae). 2 records from Rediscovery of Glenurus incalis Banks (Neuroptera: Myrmeleontidae), and notes on the Brazilian species of Glenurus Hagen. 1 records from A new species of the genus Larutia (Squamata: Scincidae) from Gunung Penrissen Sarawak, Borneo. 48 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 1212 records from Records of Halicarcinus planatus at sub-Antarctic regions. 1694 records from Herbier National de Guinée (HNG). 1 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 21 records from New records of Stenopygium Becker (Diptera: Dolichopodidae) from the Neotropical Region, and a key to species. 4445 records from Iowa State University Fishes Collection. 299 records from EDIT - ATBI in Gemer area (Slovakia). 3 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 596 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 48 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 2 records from Taxonomy of the Cixiidae (Hemiptera, Fulgoromorpha) from the Madeira archipelago. 5 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 2 records from MGC Herbarium of University of Malaga (Spain): MGC-Lichen dataset. 10749 records from WOLL AVH data. 3 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 1389 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM (Aves). 2 records from A new species of leaf-toed gecko (Phyllodactylidae, Phyllodactylus) from Maria Cleofas Island, Nayarit, Mexico. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 1593 records from Millenium Seedbank (MSB). 34 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 3 records from Latheticomyia Wheeler (Diptera: Pseudopomyzidae) from Peru: new species, description of the male of L. longiterebra Hennig and a key to species. 572 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 156 records from SOVIET ANTARCTIC EXPEDITIONS for Zooplankton (R.V. OB March-May 1956, January-March 1957;R.V.ACADEMIC KURCHATOV, October 1971-January 1972; RV DMITRY MENDELEEV;R.V.ACADEMIC IOFFE 1992).. 21197 records from Colección de Peces de Agua Dulce del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 3 records from Revision of the Diplommatinidae (Gastropoda: Cyclophoroidea) from Java. 35 records from New species of Ochodaeus Dejean from Madagascar II (Coleoptera: Scarabaeoidea: Ochodaeidae). 168469 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 115 records from Crustacea ZMK. 2 records from Revision of Scelio pulchripennis - group species (Hymenoptera, Platygastroidea, Platygastridae). 3 records from Three new species of the subterranean genus Guiodytes from Guangxi, China (Coleoptera: Carabidae: Clivinini). 92 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 1 records from Anemone pindariensis (Ranunculaceae), most recently described from the western Himalaya in India, is a teratological form of A. rivularis. 861 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herbário Virtual REFLORA. 31 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 4795 records from ICEL (Land - Invertebrates). 5 records from Two new species of the genus Microlysias (Crustacea, Amphipoda, Tryphosidae) from Korean Waters. 22735 records from UTEP Herpetology (Arctos). 1 records from Revision of the genus Miridiba Reitter, 1902 (Coleoptera, Scarabaeidae, Melolonthinae): genital morphotypes and new taxonomic data. 11836 records from Biological Reference Collections ICM-CSIC. 2 records from First Record of Dericorys albidula Serville, 1838 (Orthoptera: Dericorythidae) in Tunisia and Libya. 2 records from Two remarkable new species of oribatid mites (Acari: Oribatida) from Acacia litter of Kerala, India. 76 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 2244 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 442587 records from Southern Ocean Continuous Zooplankton Recorder (SO-CPR) Survey. 3 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 2380 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 1 records from Ichthyologie ZMK. 6 records from Description of a new Aemene Walker, 1854 from North Thailand and Myanmar, with a checklist of the genus (Lepidoptera, Erebidae, Arctiinae). 30 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 6666 records from Colección de Bruniales, Buxales, Canellales y Caryophyllales del Museo Botánico CORD - IMBIV. 954 records from NW Pacific Deep-sea Benthos Biodiversity (Beneficial Project). 6 records from Revision of the Ulopinae leafhoppers (Hemiptera: Cicadellidae) of the Indian subcontinent, I. Ulopini genera: Daimachus, Radhades and Ulopsina. 1 records from Checklist and a new species of Lippia (Verbenaceae) from the Diamantina Plateau, Minas Gerais, Brazil. 6003 records from K-State Museum of Entomological and Prairie Arthropod Research. 2 records from A taxonomic revision of the catshark genus Haploblepharus Garman 1913 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 4 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 5018 records from Colección Entomológica del Programa de Biología - Universidad de Caldas (CEBUC). 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 684 records from Estudio de la diversidad genética y su distribución de los maíces criollos y sus parientes silvestres en Michoacán (Maíz). 56 records from Cethosia myrina butterfly specimens at Museum Zoologi Bogor, Indonesia. 4 records from Two species of Ceradocus collected from coastal areas in Japan, with description of a new species (Crustacea: Amphipoda: Maeridae). 1970 records from Dipterists Forum: Field Week 1981 (Kent). 313 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 41320 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 3 records from Two new species of freshwater crabs from the highlands of northern Uganda, East Africa and a redescription of Potamonautes amalerensis (Rathbun, 1935) stat. rev. from Mount Kadam (Brachyura: Potamoidea: Potamonautidae). 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 124 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 2 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 23 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 2126 records from Dolichopodidae of Portugal - dataset 2009-2018. 4 records from 994. NICOTIANA INSECTICIDA. 1914 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 991 records from Colección Hidrobiológica del Chocó. 1 records from New species of Adeonellopsis (Bryozoa: Adeonidae) from southern Zealandia and the western Tasman Sea. 5 records from Eryngiopus Langroudiensis N. Sp. (Acari: Stigmaeidae) From Guilan, Iran. 4 records from Restoration of the genus Hampsonascia Volynkin (Lepidoptera: Erebidae: Arctiinae: Lithosiini) with descriptions of five new species. 27663 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 6 records from Caracterização do grupo Edessa rufomarginata e descrição de sete novas espécies (Heteroptera, Pentatomidae, Edessinae). 3 records from New species of Australopericoma Vaillant (Diptera: Psychodidae) from the Brazilian semiarid region and key to males of the genus. 1727 records from Herbarium of the Prioksko-Terrasnyi Biosphere Reserve. 4 records from Two New Shallow-water Species of Agathotanais (Crustacea: Tanaidacea) from Japan. 1 records from First report of the genus Longipalpus Montrouzier, 1861 (Coleoptera: Cerambycidae: Cerambycinae) from India with the description of a new species. 374 records from Collection Aves (bird skeletons) SMF. 32 records from The Plecoptera of Panama. III. The genus Anacroneuria (Plecoptera: Perlidae) in Panama’s national parks: 2017 survey results. 1 records from Two new Afrotropical genera of Scatopsidae (Diptera). 3643 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 872 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 2 records from Description of three new species of Encyrtidae Walker (Hymenoptera: Chalcidoidea) from India. 279 records from A revision of the water beetle genus Hydraena Kugelann for southern Africa (Coleoptera: Hydraenidae). 2 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 450 records from 2020_nsmk_smpl_sw_450. 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009 (Región golfo centro). 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 27 records from Jervois and Karinga Flora. 5 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 12869 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (FCME_AL). 5 records from Deep-sea Echinoderidae (Kinorhyncha: Cyclorhagida) from the Northwest Pacific. 1 records from Two new genera and two new species of cicadas from Central America (Hemiptera: Cicadidae: Cicadinae). 3 records from Descriptions of species of Acrobeles von Linstow, 1877 (Nematoda, Rhabditida, Cephalobidae) from Kelso Dunes, Mojave National Preserve, California, USA. 20 records from Five new species and a new record of Sathytes Westwood from eastern China (Coleoptera: Staphylinidae: Pselaphinae). 1 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 311 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 4 records from A new species of genus Prosopigastra A. Costa (Hymenoptera: Crabronidae: Crabroninae) from China, with a key to the Chinese species. 40 records from Moniliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 561 records from Pachliopta butterfly specimens at Museum Zoologi Bogor, Indonesia. 25 records from DNA barcoding and morphology reveal a new cryptic species of Nagiella (Lepidoptera, Crambidae, Spilomelinae) from Japan. 6977 records from 2019_NSMK_PL_2. 7 records from A new genus and eight new species of tail-wagger snails from eastern South Africa, with a key to genera within Sheldonia s. l. (Gastropoda: Urocyclidae). 6 records from Three new species of Poecilosclerida (Porifera, Demospongiae, Heteroscleromorpha) from the Aleutian Islands, Alaska. 48 records from Squid collection from 1995/96 V4 BROKE. 174 records from The empidoid flies (Diptera: Empidoidea, exclusive of Dolichopodidae) of the Russian Arctic islands and Svalbard Archipelago. 1 records from Hydroporus novacula sp. n. from Georgia (Caucasus) (Coleoptera, Dytiscidae Hydroporini) - the first terrestrial species of the genus?. 6241 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 4 records from A new species of Ferorhinella (Hemiptera: Cercopidae) from southeastern Brazil with taxonomic notes on the genus. 150 records from Invertebrados y aves playeras de la Laguna Madre de Tamaulipas, México (Poliquetos). 8 records from On two enigmatic spiders (Araneae: Cybaeidae & Phrurolithidae) from the Russian Far East. 2 records from New Black Fungus Gnats (Diptera, Sciaridae) of North America. Part II. Genus Bradysiopsis Tuomikoski, 1960. 1 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 3472 records from Microhabitat distribution of arboreal oribatid mites (Oribatida), associated with the Siberian pine (Pinus sibirica) of Western Siberia.. 2 records from The genus Lyroda Say, 1837 in Africa and Arabian Peninsula with description of two new species (Hymenoptera, Crabronidae). 1 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 11492 records from Collection Pisces SMF. 18 records from JOHN W. BROWN (2019) New genera, new species, and new combinations in new world Cochylina (Lepidoptera: Tortricidae: Tortricinae). Zootaxa, 4671 195 - 222.. 1 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 2 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 67 records from MEXU/Tipos de plantas vasculares. 27 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 4 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 2 records from Four new genera of the Ceratonotus group (Copepoda, Harpacticoida), including the description of two new species. 4414 records from ESA herbarium - Universidade de São Paulo - Herbário Virtual REFLORA. 1 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 197 records from Collection of Heteroptera. 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 2 records from Stephanodiscus Ehr. species from Holocene sediments in the Faiyum Depression (Middle Egypt). 14149 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 3 records from A new species of Alonella Sars, 1862 (Crustacea: Cladocera: Chydoridae) from the Ecuadorian Andes. 15 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 15 records from Checklist of Cerambycidae (Coleoptera) primary types of the Coleção Entomológica Pe. Jesus Santiago Moure, Departamento de Zoologia, Universidade Federal do Paraná, Curitiba, Paraná, Brazil, Instituto Nacional de Pesquisas da Amazônia, Amazonas, Manaus, Brazil, and of the Museu Paraense. 2 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 27147 records from UAZ Mammals. 1 records from First Record of Holothuria (Cystipus) dura (Echinodermata: Holothuroidea) from Japan, with Notes on Locomotion. 4647 records from Swedish Malaise Trap Project (SMTP) - Dolichopodidae. 15 records from Modelaje de la distribución potencial de 10 especies de anfibios y reptiles en riesgo de extinción con escasos registros de presencia (ANONAU). 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 2 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 4735 records from López-Uribe Lab Collection. 434 records from A revision of the minor species group in the millipede genus Nannaria Chamberlin, 1918 (Diplopoda, Polydesmida, Xystodesmidae). 3 records from Actualización de la base de datos de colémbolos de México. 19 records from A new species of tadpole-goby, Benthophilus persicus sp. nov. (Teleostei: Gobiidae) from the southern Caspian Sea. 5 records from Order Diptera, family Mydidae. 336 records from Malawi-Saturniidae-Biodiversity-Data. 7 records from On the Neotropical spider genus Tullgrenella Mello-Leitão, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 13 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 175 records from Bird specimens of Obihiro Centennial City Museum. 38271 records from Botanical Museum, Copenhagen, Mycology Herbarium. 3 records from Description of three new velvet geckos (Diplodactylidae: Oedura) from inland eastern Australia, and redescription of Oedura monilis De Vis. 5 records from Genome sequencing reveals extraordinary cephalic horns in the Madagascan dung beetle genus Helictopleurus (Coleoptera, Scarabaeinae): insight from a revision of fungicola species group. 1266 records from Catálogo de los mamíferos de México en resguardo de The Natural History Museum (London), Inglaterra. 5 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 24 records from Estructura genética poblacional de las especies de Tapaojitos (Aves Parulinae: Geothlypis) que ocurren en los humedales de México: Uno de los hábitats más amenazados de nuestro país. 55482 records from Fish Specimens. 18 records from New species of Chimaera (Chondrichthyes: Holocephali: Chimaeriformes: Chimaeridae) from the Southwestern Indian Ocean. 24 records from Novitates neocaledonicae XII: Two additional new species of Cryptocarya R. Br. from New Caledonia. 11282 records from NCSM Mammalogy Collection. 23 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 4 records from Two new species of the genus Scaphidium Olivier (Coleoptera: Staphylinidae Scaphidiinae) from Southwest China. 2380 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 2 records from Plectranthias cruentus, a new species of anthiadine perchlet (Teleostei: Serranidae) from the Lord Howe Rise, Tasman Sea. 101 records from Fungal Bioblitz in Białowieża Primeval Forest at 18th Congress of European Mycologists. 30752 records from DIPOL. 1789 records from Colección Zoológica de la Universidad del Tolima (CZUT)- Mastozoología. 183248 records from Tasmanian Museum and Art Gallery provider for OZCAM. 938 records from TTRS Mammals. 15208 records from UAM Invertebrate Collection (Arctos). 1 records from Diglotta mersa (Haliday) and Halobrecta flavipes Thomson, two new species for the Canadian fauna (Coleoptera, Staphylinidae, Aleocharinae). 1 records from Review of Neoanchisquilla Moosa, 1991 and Neclorida Manning, 1995 (Crustacea: Stomatopoda: Squilloidea), with descriptions of two new species of Neoanchisquilla from the Indian Ocean. 436 records from World revision of Iteaphila with unbranched radial vein (Diptera: Empidoidea: Iteaphilidae). 5 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 6 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 12 records from Sexual variation in two species of Helorus Latreille (Hymenoptera, Heloridae) from NW China, with description of female of Helorus caii He & Xu. 19 records from Colección Ornitológica del Museo de Historia Natural de la Universidad de la Amazonia. 1774 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling]). 427 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 3 records from A new Hasemania Ellis from the upper rio Paraná basin, with the redescription of Hasemania crenuchoides Zarske & Géry (Characiformes: Characidae). 2800 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 453 records from Revision of Anisepyris Kieffer (Hymenoptera, Bethylidae), with description of 135 new species. 1 records from First finding of the shrimp genus Harperalpheus Felder & Anker, 2007 in the eastern Pacific, with description of a new species from Bahía Málaga, Colombia (Malacostraca: Decapoda: Alpheidae). 3 records from Three new species of Willowsia (Collembola: Entomobryidae) from Guizhou Province, China. 9 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 13 records from Deux espèces nouvelles de Thiollierea Montrouz. (Rubiaceae), endémiques des massifs Nord-Ouest de la Grande Terre (Nouvelle-Calédonie). 4 records from Megymenum tuberculatum, a new species of Megymenini from Java and a review of distribution of M. brevicorne (Hemiptera: Heteroptera: Dinidoridae). 2 records from Description of Two New Species of Baeocera Erichson (Coleoptera: Staphylinidae: Scaphidiinae) from México. 6 records from New State and Host Records for Agromyzidae (Diptera) in the United States, with the Description of Ten New Species. 92820 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 1 records from Two new species of comb-clawed beetles (Coleoptera: Tenebrionidae: Alleculinae) from Yunnan, China. 155 records from artsprosjektet_45-15_helvella. 29 records from University of Sindh Jamshoro Herbarium. 5 records from The unknown diversity of the genus Characidium (Characiformes: Crenuchidae) in the Chocó biogeographic region, Colombian Andes: Two new species supported by morphological and molecular data. 2 records from A New Genus of the Spider Family Caponiidae (Araneae, Haplogynae) from the West Indies. 7 records from On the taxonomic validity of Indian ground spiders: I. Genus Scopoides Platnick, 1989 (Araneae: Gnaphosidae). 1259 records from Bryozoa, Brachiopoda and Entoprocta (TSZBr) UiT Tromsø Museum. 28 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 1 records from Two new species of the bamboo-feeding planthopper genus Arcofacies Muir (Hemiptera: Fulgoroidea: Delphacidae) from China. 37 records from Revision of the genus Doryscus Jacoby (Coleoptera: Chrysomelidae: Galerucinae). 9 records from New species and records of Cladiopsocus Roesler (Psocodea: ‘ Psocoptera’: Psocomorpha: Cladiopsocidae) from Colombia. 13 records from Bothynus entellus (LePeletier & Serville) (Coleoptera: Scarabaeidae: Dynastinae) species group: taxonomic revision and description of two new species. 59 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 2 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 3042 records from Herpetile collection NTNU University Museum. 3 records from Onthophagus fragosus n. sp. a second endemic species of Onthophagus Latreille from Cuba (Coleoptera: Scarabaeidae, Scarabaeinae). 2980 records from Colección de Peces Universidad Católica de Oriente. 13 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 641 records from Fitoplancton marino frente a Baja California. 2. Áreas de surgencias de la región Ensenadense. 4 records from Two new species of Oxynoemacheilus from the Tigris drainage in Iraqi Kurdistan (Teleostei: Nemacheilidae). 18 records from Aves de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 1 records from A taxonomic revision of the genus Thalia Blumenbach, 1798; Weelia Yount, 1954; Brooksia Metcalf, 1918 (Salpida: Salpidae) from East Coast of Peninsular Malaysia. 6958 records from Ecología y biogeografía de epífitas vasculares de Chiapas, México. 4211 records from VIC - Herbário da Universidade Federal de Viçosa. 23 records from Contribution to the knowledge on the genus Barsine Walker, 1854 from mainland China and Indochina, with description of a new species (Lepidoptera, Erebidae, Arctiinae, Lithosiini). 91478 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 4 records from A new species of Carpenter Moths (Lepidoptera, Cossidae) from Tarbagatai (NE Kazakhstan) and Altai (SW Siberia, Russia) Mountains. 2 records from New Vietnamese Species Of The Genus Flavoperla Chu (Plecoptera: Perlidae). 7 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 4 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 331 records from Hydraenidae of Madagascar (Insecta: Coleoptera). 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 2 records from A new species of the Gekko japonicus group (Squamata: Gekkonidae) from central Laos. 141733 records from Arctic Ocean Diversity. 6 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 17 records from New species of Duplominona Karling, 1966 (Platyhelminthes, Proseriata) from the Pacific coast of Panama. 1 records from Sinoperlodes, a new genus of subfamily Perlodinae (Plecoptera, Perlodidae) from coastal southeastern China. 3 records from Eleven new species and a new country record of Pselaphodes (Coleoptera: Staphylinidae: Pselaphinae) from China, with a revised checklist of world species. 4207 records from CASES2003_2004. 376 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Xiloteca). 7 records from Two new species of Batrisodes Reitter from Shaanxi, China (Coleoptera Staphylinidae: Pselaphinae). 114 records from A second update to the checklist of Finnish long-legged flies (Diptera: Dolichopodidae), with a re-evaluation of the status of Hydrophorus callosoma Frey, 1915. 2 records from Physaloptera apodemi sp. nov. (Nematoda: Physalopteridae) from Apodemus sylvaticus (Linnaeus, 1758) (Rodentia: Muridae) from Tianjin, China. 54 records from CHAS Botany Collection (Arctos). 1 records from Plant collection Natuurmuseum Brabant, Tilburg. 4 records from Leuctra Pinhoti, A New Species Of Stonefly (Plecoptera: Leuctridae) From Alabama, U. S. A.. 9 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 5 records from A new species of Contarinia (Diptera: Cecidomyiidae) damaging inflorescence of Carya cathayensis (Juglandaceae) in China. 10 records from A revision of Pinobius. II. Three new species from Cambodia and Indonesia, and additional records (Coleoptera: Staphylinidae: Paederinae). 10 records from Revision of Pyrrhalta (Coleoptera: Chrysomelidae: Galerucinae) species with maculate elytra. 1 records from A taxonomic revision of Gymnothorax undulatus (Anguilliformes: Muraenidae) in the Western Indian Ocean, with description of a new species. 7 records from A new species of the genus Goera Stephens (Trichoptera, Goeridae) found in madicolous habitats in Amami-Oshima, southwestern Japan. 1 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 1512 records from Données d'occurrence de la flore du Sénégal (Acanthaceae - Chenopodiaceae), Herbier IFAN. 821 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 18 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 2 records from Bryoerythrophyllum subcaespitosum (Pottiaceae), a new combination for a neglected species from South America. 5 records from Notes on Indian wolf spiders: I. Genus Evippa Simon, 1882 (Araneae: Lycosidae Evippinae). 53 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 12 records from Three new species of Seira Lubbock (Collembola, Entomobryidae, Seirinae) from Madagascar with Lepidocyrtus - like habitus. 6710 records from Odonata de Veracruz. 324 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 6 records from Revisions to the faunas of Andrena of the Iberian Peninsula and Morocco with the descriptions of four new species (Hymenoptera: Andrenidae). 65 records from A review of the genus Cyana Walker, 1854 from India, with descriptions of five new species and three new subspecies (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 4 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 1739 records from Colección de Cnidarios del Museo de Historia Natural Marina de Colombia - Makuriwa. 968 records from HDCF herbarium - Universidade Federal de Santa Maria - Herbário Virtual REFLORA. 8 records from Five new genera of the subfamily Psilodercinae (Araneae: Ochyroceratidae) from Southeast Asia. 15 records from Traumatomutilla André miscellanea: Revision of the bellica, bifurca, diabolica, and vitelligera species groups, and a new group for the new species T. pilkingtoni Bartholomay and Williams (Hymenoptera: Mutillidae: Sphaeropthalminae: Dasymutillini). 4 records from Reconsideration of the genera Merogomphus Martin, 1904, and Anisogomphus Selys, 1857, including erection of a new genus, with a new species and discussion of additional specimens from Cambodia. 5 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 5 records from CIRAD. 2 records from A new species of Hieracium sect. Pannosa (Asteraceae) from Bulgaria. 2 records from Zaitzevia tangliangi sp. nov. a new riffle beetle from China (Coleoptera: Elmidae Macronychini). 53 records from Base de datos de las familias Compositae y Umbelliferae. Donación del Herbario Kew. 6 records from Moribaetis brachiostrinus (Ephemeroptera: Baetidae), a new species of mayfly from Costa Rica. 36 records from Three new species of Parapercis (Perciformes: Pinguipedidae) and first records of P. muronis (Tanaka, 1918) and P. rubromaculata Ho, Chang & Shao, 2012 from Australia. 3 records from Nouveautés dans le genre Lomariopsis Fée (Pteridophyta, Lomariopsidaceae) à Madagascar: trois espèces nouvelles et une espèce africaine nouvellement signalée. 2612 records from Fungi specimens of Saitama Museum of Natural History. 2 records from Yunnan-Guizhou Plateau: a mycological hotspot. 2 records from Leptagrion itabaiana sp. nov. (Odonata: Coenagrionidae) from Serra de Itabaiana National Park, Sergipe state, Northeastern Brazil. 1 records from A new species of Leiochrides Augener, 1914 (Annelida: Capitellidae) from the Beibu Gulf, South China Sea. 6 records from A New Species Of Perlesta (Plecoptera: Perlidae) From New York. 21 records from Siphonoecetinae (Crustacea: Amphipoda: Ischyroceridae) 7: Australian Concholestids, Ambicholestes n. gen., with a Description of Six New Species, and a New, Restricted Diagnosis for Caribboecetes Just, 1983. 2 records from Two new species of the genus Chironephthya (Octocorallia, Alcyonacea, Nidaliidae Siphonogorgiinae) from the Gulf of Thailand. 9 records from New distribution records of the genus Saga Charpentier, 1825 (Orthoptera Tettigoniidae: Saginae) from Iraq. 25 records from New species and records of Entomobryidae and Orchesellidae (Collembola) from the East Caucasus (Russia). 10 records from Contribution to the knowledge of Carabidae in Iran with the descriptions of five new taxa, proposing of four synonyms and providing of nine new records (Insecta: Coleoptera). 1 records from A taxonomic note of Pterocephalus (Caprifoliaceae) from N Iran. 1 records from Micromacrocera Gen. N., The Smallest Macrocerine Fly (Diptera: Keroplatidae, Macrocerinae). 1 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 1515 records from Mammals in the collection of Zoological Museum of NSNHM (the National Science and Natural History Museum at the National Academy of Sciences of Ukraine, Kyiv): Erinaceidae, Talpidae, Soricidae, Myoxidae, Sminthidae. 2 records from Two new species of Bucculatrix Zeller (Lepidoptera: Bucculatricidae) from China. 4 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 1 records from A new species of Microhyla Tschudi, 1838 (Anura: Microhylidae) from West Coast of India: an integrative taxonomic approach. 52 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 5 records from Taxonomic revision of Stagmatoptera Burmeister, 1838 (Mantodea: Mantidae, Stagmatopterinae). 11698 records from Bell Museum fungi. 2 records from Colletes alborzensis nov. sp., a new bee species from Iran (Hymenoptera, Colletidae). 2 records from Amphibian specimens of Obihiro Centennial City Museum. 1 records from Discovery of a third species of Lamproptera Gray, 1832 (Lepidoptera: Papilionidae). 37691 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 2 records from Cyana fossi, a new species from Vietnam (Lepidoptera: Erebidae: Arctiinae Lithosiini). 1 records from Pentatomiana beckerae gen. nov. and sp. nov., a new Neotropical Pentatomini (Hemiptera, Heteroptera, Pentatomidae). 19 records from Redescription of the Indo-West Pacific cardinalfishes (Perciformes: Apogonidae) Rhabdamia spilota Allen & Kuiter 1994 and R. gracilis (Bleeker 1856). 425 records from Collection ornithologique A. Maës. 30 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 1 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 5300 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 4 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 36 records from Mammal specimens of Komatsu City Museum. 33 records from A review of the genus Hexachaetoniella Paschoal in Australia (Acarina: Cryptostigmata: Pedrocortesellidae). 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 8 records from Two new species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Kurile Islands, Sea of Okhotsk, with a review of distinctive characters of the known species of the genus. 13 records from Records Of Anacroneuria (Plecoptera: Perlidae) From Bolivia And Paraguay With Descriptions Of Three New Species. 6057 records from 2018_nsmk_biodiversity_pi. 1 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 6 records from Two new species of bent toed geckos, Cyrtodactylus Gray, 1827 (Squamata: Gekkonidae) from Northeast India with comments on name-bearing types from the region. 6 records from Two new species of Coeliccia Kirby from Yunnan, China (Odonata: Zygoptera Platycnemididae). 4 records from Taxonomic review of the ant genus Dilobocondyla from China (Hymenoptera: Formicidae), with a revised key to the known species. 2 records from First record of Bouvieraxius keiensis Sakai, 1992 and Manaxius aurantiaca n. sp (Decapoda: Axiidea) from the waters around the Ogasawara Islands, Japan. 13 records from Descriptions of two new genera of Maruinini (Diptera, Psychodidae, Psychodinae) from the Mitaraka range of French Guiana. 9 records from Taxonomic review of the genus Lista Walker, 1859 from China (Lepidoptera, Pyralidae, Epipaschiinae), with descriptions of five new species. 1 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 3 records from Morphological and molecular evidence for a new species of the genus Panolis Hübner, [1821] (Lepidoptera: Noctuidae). 961 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 1283 records from Barcant Butterfly Collection - Nymphalidae. 12 records from Mamíferos del municipio de Santa Bárbara, Santander - Proyecto Santander BIO. 11494 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Entomologica). 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 2 records from Redescription of Admete sadko Gorbunov, 1946 (Gastropoda: Cancellariidae). 132486 records from Herbarium of Taiwan Forestry Research Institute. 1 records from Three new species, a lectotype designation, and taxonomic and geographic notes in Eburiini (Coleoptera, Cerambycidae, Cerambycinae). 2 records from Basothorhynchus, a new Oosomini genus from the highland plateau of Lesotho (Coleoptera: Curculionidae: Entiminae). 3 records from Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand. 2 records from New Notophthiracarus species (Acarina, Oribatida, Phthiracaridae) and overview of the distribution of the genus in South Africa. 433 records from Flora del Valle de Tehuacán-Cuicatlán: III fase. 242 records from Malawi-Histeridae-Biodiversity-Data. 942 records from Caracterización biológica de la ventana Beltrán, corregimiento Paquiló, Municipio de Beltrán, Cundinamarca. 3700 records from Swiss National Diplopoda Databank. 25 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 4438 records from Occurrence data set of Non-Timber Forest Products species for medicinal purposes in Zimbabwe’s biodiversity hotspots. 168 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 2 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 4 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 1 records from A new species of the genus Mongolotettix Rehn, 1928 from Hubei, China (Acrididae, Acridoidea, Orthoptera). 4 records from Two new species of the banjo catfish Bunocephalus Kner (Siluriformes: Aspredinidae) from the upper and middle rio São Francisco basins, Brazil. 8 records from Diversidad de bacterias fotótrofas en comunidades microbianas bentónicas de Bahía Concepción, BCS, México. 2 records from From marine caves to the deep sea, a new look at Caminella (Demospongiae, Geodiidae) in the Atlanto-Mediterranean region. 22 records from BIRDRACE Birding Bentheim. 1 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 276 records from Equinodermos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMeq-UV). 34 records from Julmarichardiidae, a new apseudoidean family (Crustacea: Tanaidacea: Apseudomorpha) with the description of a new species of Julmarichardia Guţu 1995 from the Northwest Australian Shelf. 201 records from The jumping plant-lice (Hemiptera: Psylloidea) of Belarus. 1 records from Tagalis graziae, a new species of Saicinae from the Chocó biogeographic region in Colombia (Hemiptera: Reduviidae). 8 records from Revision of Pseudexogone Augener, 1922 (Annelida, Polychaeta, Syllidae), and its transfer to Pilargidae. 3 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 1139 records from SWECO. 159 records from Taxonomic review of Tipula (Vestiplex Bezzi) crane flies (Diptera: Tipulidae) in Mongolia. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 1 records from Taxonomic review of Stictophaula (Orthoptera: Phaneropterinae) with the description of one new species from Brunei Darussalam. 16833 records from EAC - Herbário Prisco Bezerra. 2 records from Estudio genético de las poblaciones de Rhizophora mangle en México. 1140 records from Flora (vascular) y fauna (aves) de los Parques Nacionales del estado de Baja California: Constitución de 1857 y Sierra San Pedro Mártir (Aves). 8 records from A new species of Nerice Walker, 1855 and further additions to the catalogue of Indian Notodontidae Stephens, 1829 (Lepidoptera: Noctuoidea) from Himalaya with report of range extensions. 6 records from Type material housed in the Carcinological Collection of the Museo de La Plata, Argentina. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 1519 records from Leif Richardson Vermont Bee Specimens. 11 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 2740 records from Olga Lakela Herbarium, University of Minnesota Duluth. 2 records from A cryptic new species of hummingbird of the Campylopterus largipennis complex (Aves: Trochilidae). 5662 records from Collection Crustacea - ZMB. 628 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 4 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 836 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 18 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 1 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 165 records from Fungal Speciments of Toyota City Nature Sanctuari (TCNS).. 6 records from Five new species of the genus Dindymus (Heteroptera: Pyrrhocoridae). 1 records from The crab spider genus Tarrocanus Simon, 1895 with notes on the genera Alcimochthes Simon, 1895 and Domatha Simon, 1895 (Araneae: Thomisidae). 87 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Tayrona. 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 1 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 2 records from Description of a new genus and four new species of Acaricalini (Acari, Eriophyidae, Phyllocoptinae) from South China. 4 records from Le genre Oxyanthus DC. (Rubiaceae) en Afrique de l’Ouest: description d’une nouvelle espèce. 1441 records from Actualización de la base de datos computarizada de la colección ictiológica de la Universidad Autónoma de Baja California. 2 records from Heteropterys rosmarinifolia, a new species of Malpighiaceae with verticillate leaves from savannas grasslands of central Brazil. 7 records from Polycentropus dinkinsorum (Trichoptera: Polycentropodidae), a newly described caddisfly species from the southern Appalachian Mountains, USA. 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 10 records from New species of Rivudiva Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae) with comments on R. minantenna Lugo-Ortiz & McCafferty and R. trichobasis Lugo-Ortiz & McCafferty. 6 records from Distribution of two species of Nephropsis Wood-Mason, 1872 (Crustacea, Decapoda, Nephropidae) from northeastern Brazil. 1222 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 25 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 26 records from On some new or rare spider species from Lesbos, Greece (Araneae: Agelenidae, Amaurobiidae, Corinnidae, Gnaphosidae, Liocranidae). 27 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 2 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 4 records from First records of Kempnyia and Macrogynoplax (Plecoptera: Perlidae) from Tocantins State, Brazil with description of the immatures and the adult female. 1 records from New collections of freshwater crabs from northern Madagascar, with the description of a new species of Foza Reed & Cumberlidge, 2006 (Brachyura, Potamonautidae), and comments on their conservation status. 15 records from New synonyms of Euconnus (Tetramelus) kraussi Reitter, 1880 (Coleoptera Staphylinidae, Scydmaeninae). 4 records from Four new species of Rhyacophila Pictet 1834 (Trichoptera: Rhyacophilidae) from Southeast Asia. 812 records from Ibaraki Nature Museum, Birds collection. 3 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 22 records from Five new and five known species of the genus Tylencholaimus de Man, 1876 (Nematoda: Dorylaimida: Tylencholaimoidea) from Western Ghats of India. 7271 records from Dipterists Forum: Field Week 2018 (Stoke). 721 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 1 records from Macropharyngodon pakoko, a new species of wrasse (Teleostei: Labridae) endemic to the Marquesas Islands, French Polynesia. 2 records from Two new species of Kamimuria (Plecoptera: Perlidae) from Shaanxi Province, China. 30 records from New species of Triplocania Roesler (Psocodea: ‘ Psocoptera’: Ptiloneuridae) from Colombia and Peru. 1 records from Grammatonotus brianne, a new callanthiid fish from Philippine waters, with short accounts of two other Grammatonotus from the Coral Triangle. 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 7 records from Two new tanaidaceans (Crustacea: Peracarida) from Portuguese submarine canyons (NE Atlantic, West Iberian Margin). 2 records from On the diversity of Terebellides (Annelida, Trichobranchidae) in West Africa, seven new species and the redescription of T. africana Augener, 1918 stat. prom.. 13290 records from Mollusca collection of National Museum of Nature and Science. 1 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 16610 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 2 records from Two new Kukri Snake species (Colubridae: Oligodon) from the Nakhon Si Thammarat Mountain Range, and addition of O. ocellatus to the fauna of Thailand. 1750 records from Colección del Herbario de la Universidad de los Llanos. 112 records from The Genus Megaleuctra Neave (Plecoptera: Leuctridae) In North America. 24 records from Peces de la expedición en el páramo de Ocetá, Boyacá - Proyecto Boyacá BIO. 1 records from Modiolus cimbricus sp. nov. (Bivalvia: Mytilidae) endemic in the Kattegat-Skagerrak. 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 4 records from Taxonomic revision of the genus Glenopopillia (Coleoptera: Scarabaeidae: Rutelinae). 1 records from A new species of the basal araneomorph spider genus Ectatosticta. 2 records from A new species of Glyphocrangon (Crustacea, Decapoda, Caridea, Glyphocrangonidae) from the Austral Islands, French Polynesia. 10 records from Two new endangered species of Polygala series Trichospermae (Polygalaceae), endemic to the Cerrado domain, Tocantins State, Brazil. 2251762 records from NMNH Extant Specimen Records (USNM, US). 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 15 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 2 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 1 records from Neoperla Of Unusual Size From Vietnam (Plecoptera: Perlidae). 177 records from Alien plants of Kyrgyzstan. 10 records from Taxonomic revision of a darkling beetles genus Anaxius (Tenebrionidae: Pedinini: Helopinina). 6755 records from Plan de vertebrados de la Patagonia. 9445 records from Collections of Phytoplankton at Herbarium Berolinense, Berlin (B). 1 records from A new species of the genus Aalatettix Zheng & Mao (Orthoptera, Tetrigoidea Tetrigidae) from China. 2 records from First record of the family Bolitophilidae (Diptera: Sciaroidea) from the Lagunas de Zempoala National Park, Mexico, with description a new species. 4 records from Two new species of Aufidus (Hemiptera, Cercopidae) from New Guinea. 1 records from A new freshwater chrysophyte, Chrysomorula cohaerens gen. et sp. nov. (Chrysophyceae, Chrysocapsaceae) from North America. 18 records from New species of Andiorrhinus Cognetti, 1908 (Oligochaeta: Rhinodrilidae) from Venezuela and Brazil. 44 records from The grasshoppers (Orthoptera, Acridomorpha) from the Mitaraka Mountain Range, French Guiana. 1 records from New enchytraeid species from Mount Hallasan (Jeju Island, Korea) (Enchytraeidae, Oligochaeta). 1 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 4 records from A new species of Paratus Simon, 1898 (Araneae: Liocranidae, Paratinae) from India. 1 records from New species of Chaetonerius Hendel (Diptera: Neriidae) from the Oriental Region. 41 records from Revision of the genus Theopea Baly (Coleoptera: Chrysomelidae: Galerucinae) in Sundaland and the Philippines: Redefinition of the genus. 13 records from The genus Semicerura (Collembola; Isotomidae) in Asia. 1 records from Dolichochorus Strobl 1904: a valid genus of Mesochorinae (Hymenoptera: Ichneumonidae: Mesochorinae). 75 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 31210 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 4 records from A new Scleromystax species (Siluriformes: Callichthyidae) from coastal rivers of Southern Brazil. 5 records from A new genus of Tetracampidae (Hymenoptera) from South Africa. 7 records from A new Subleuconycta (Lepidoptera: Noctuidae: Acronictinae) species from Taiwan. 4566 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 794 records from Carabidae of the European North-East of Russia. 19 records from A new species of the genus Tetragonopterus Cuvier, 1816 (Ostariophysi: Characiformes: Characidae) from the rio Tocantins drainage, Brazil. 1698 records from Invertebrate collection of University of Oulu Zoological Museum. 4038 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 7 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 1 records from A revision of the genus Paraleptognathia Kudinova-Pasternak, 1981 (Crustacea: Tanaidacea) and description of four new species. 3984 records from FBIP: Diversities of microbiomes from South African arid and natural soils. 86130 records from University of New Mexico Herbarium. 1 records from Dermatopelte Erdös & Novicky (Hymenoptera: Eulophidae) newly recorded from the Nearctic region, with description of two new species. 1 records from Notes on taxonomy and distribution of some Palaearctic Ancylosis Zeller, 1839 (Lepidoptera: Pyralidae: Phycitinae). 1 records from The genus Chionanthus (Oleaceae) in Cambodia, Laos and Vietnam. 1 records from New records of family Hormathiidae (Cnidaria: Actiniaria) from Brazilian coast with description of Paraphelliactis labiata n. sp.. 135 records from Colección de Quelonios Museo de La Salle Bogotá (MLS). 1 records from Description of the mature larva and pupa of Ora semibrunnea Pic (Coleoptera: Scirtidae) with notes on its biology. 10 records from Novel taxa of Cheilostomata Bryozoa discovered in the historical backlogs of the Iziko South African Museum. 9 records from Cryptic species in the nuisance midge Polypedilum nubifer (Skuse) (Diptera: Chironomidae) and the status of Tripedilum Kieffer. 11 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 25430 records from Bryophyta collection of the Botanical Museum of the University of Oulu. 46 records from ffie South American Goblin Spiders of the New Genera Pseudodysderina and Tinadysderina (Araneae, Oonopidae). 25 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 3976 records from COR herbarium - Universidade Federal de Mato Grosso do Sul / Campus Pantanal - Herbário Virtual Reflora. 3 records from The Amphipoda (Crustacea) of New Caledonia: Aoridae. 23665 records from La colección briológica del Herbario Nacional (MEXU). Actualización 2000. 3 records from Nomenclatural notes on some currently known species of Eupogonius LeConte, 1852 (Coleoptera: Cerambycidae: Lamiinae) and description of seven new species. 13 records from Perot Museum of Nature and Science. 5 records from Two new species of Carcinoplax H. Milne Edwards, 1852, and Pycnoplax Castro, 2007, from the western Pacific, and a description of the female of Thyraplax truncata Castro, 2007 (Crustacea, Decapoda, Brachyura, Goneplacidae). 100249 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 7 records from The Neotropical genus Cyriocosmus Simon, 1903 and new species from Peru, Brazil and Venezuela (Araneae: Theraphosidae: Theraphosinae). 2 records from On the sun-spiders of the ibirapemussu species-group of the genus Gaucha Mello-Leitão, 1924 (Solifugae, Mummuciidae), with description of a new species. 4 records from Two new species of the genus Sinopodisma (Orthoptera: Acridoidea: Catantopidae: Podisminae) from China. 1613 records from Phragmites of Canada. 11 records from New Species And New Records Of Xiphydriid Woodwasps (Hymenoptera: Xiphydriidae) From Southeastern Asia. 5 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) VIII. The densimacularis species group, with descriptions of four new species. 10 records from Description of two new species of Regalana and a new genus of Gyponini (Hemiptera: Cicadellidade: Iassinae). 1 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 3 records from Taxonomic revision of the P. chartergoides species-group of the genus Protopolybia Ducke, 1905 (Hymenoptera: Vespidae, Polistinae). 8 records from New records of the water mite genus Arrenurus Dugès, 1834 from South America (Acari: Hydrachnidia: Arrenuridae), with the description of five new species and one new subspecies. 25 records from Nomenclatural notes on Cryptocarya R. Br. (Lauraceae) from Madagascar. 4 records from A new species of Victrix Staudinger, 1879 from Kazakhstan (Lepidoptera, Noctuidae). 216 records from Admiralty Bay Benthos Diversity Data Base (ABBED). Polychaeta. 1979-80. 12 records from Revision of Anomalomorpha Arrow, 1908 and Enracius Dechambre, 1999, with Erbmahcedius new genus from southeastern Australia (Coleoptera: Scarabaeidae: Dynastinae: Pentodontini: Cheiroplatina). 1 records from Monsters in the dark: systematics and biogeography of the stygobitic genus Godzillius (Crustacea: Remipedia) from the Lucayan Archipelago. 1 records from Zorotypus huangi sp. nov. (Zoraptera: Zorotypidae) from Yunnan, southern China. 4 records from A new species of Versicorpus Deschodt, Davis & Scholtz, 2011 (Scarabaeidae Scarabaeinae: Byrrhidiini) from the Brandberg Mountain, Namibia. 12124 records from UCSC Herbarium - Kenneth S. Norris Center for Natural History, University of California Santa Cruz. 2 records from A new pea crab species of the genus Arcotheres Manning, 1993 (Crustacea: Decapoda: Brachyura: Pinnotheridae) from India. 65 records from Contribution to the knowledge of the Nolini of the Maputo Special Reserve in South Mozambique with description of two new species and several taxonomic updates (Lepidoptera, Nolidae, Nolinae). 25884 records from JCT AVH data. 1 records from Revision of the genus Bradyporus Charpentier, 1825 (Orthoptera: Tettigoniidae: Bradyporinae). 2 records from New records, taxonomic notes, and the description of a new species of Reduviidae (Hemiptera: Heteroptera) from Ecuador. 1165 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009 (Región centro). 2 records from A new species of Goniacerini from Cameroon (Coleoptera: Staphylinidae: Pselaphinae). 12 records from An of Zelotibia (Araneae, Gnaphosidae), a spider genus with a species swarm in the Albertine Rift. 85920 records from University of Tennessee Bryophyte Herbarium. 2 records from A new species of the Goblin Spider genus Predatoroonops Brescovit, Rheims & Ott 2012 (Araneae, Dysderoidea: Oonopidae), with new records for the genus. 6265 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 179 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 3 records from New sciaphilic plakinids (Porifera, Homoscleromorpha) from the Central-Western Pacific. 23 records from Exceptional diversity of Tischeriidae (Lepidoptera) from a single tropical forest site in Belize, Central America. 19 records from Polysyncraton (Ascidiacea, Didemnidae): a re-examination of some specimens and descriptions of three new species. 13094 records from Royal Belgian Institute of Natural Sciences Mollusc collection. 149 records from The Geometridae of Ethiopia III: genus Zamarada (Lepidoptera: Geometridae Ennominae, Cassymini). 8 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 6 records from A revision of the clam shrimp Australimnadia Timms and Schwentner, 2012 (Crustacea: Spinicaudata: Limnadiidae) with two new species from Western Australia. 7 records from Revisão do gênero Antiteuchus Dallas (Heteroptera, Pentatomidae, Discocephalinae). 4 records from Bulbophyllum section Rhytionanthos (Orchidaceae) in Vietnam with description of new taxa and new national record. 6417 records from Colección de anfibios y reptiles, Universidad del Valle (Colección UV-C). 4 records from Collection Myriapoda - SNSD. 122 records from Colección de Salamandras Museo de La Salle Bogotá (MLS). 2 records from Notes on the subspecies of Plagionotus arcuatus (Linnaeus, 1758) with description of a new subspecies from Iran (Coleoptera: Cerambycidae). 11333 records from Colección de referencia de vectores de Leishmania spp (causante de Leshmaniasis cutánea localizada) de la Península de Yucatán y un estudio preliminar en un área endémica de Quintana Roo (UADY). 1 records from Homalometron moraveci n. sp. (Digenea: Apocreadiidae) in the yellowfin goatfish, Mulloidichthys vanicolensis (Valenciennes, 1831) (Perciformes: Mullidae), from New Caledonia and the Great Barrier Reef, with a checklist of digeneans of Mulloidichthys species. 149 records from A revision of the genus Drasteria of Central Asia and Kazakhstan with special attention to the adjacent areas (Lepidoptera: Erebidae). 4 records from Revision der Gattung Agachila D & G - M, 1954 (Hemiptera: Heteroptera: Tingidae). 3 records from First record of the genus Microstenus Szépligeti (Hymenoptera: Ichneumonidae Cryptinae) from China, with description of one new species and a key to world species. 1 records from Leptomischus anisophyllus (Argostemmateae: Rubiaceae), a new species from Vietnam. 14 records from Hétérocères de La Réunion. 25 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 62 records from R-Fungi - Herbário do Museu Nacional. 8 records from A new large-bodied, rupicolous Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) allied to Cnemaspis heteropholis Bauer, 2002 from the Central Western Ghats of Karnataka, India. 70 records from Contrasting species diversification of Eutarsopolipus (Acariformes: Podapolipidae) on Castelnaudia and Notonomus (Coleoptera: Carabidae). 1914 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 2 records from Description of the male of Antodice quadrimaculata Martins & Galileo, 2003 (Coleoptera, Cerambycidae, Lamiinae), with new country record for the species. 36535 records from LSUMZ Mammals Collection. 1 records from First data on the bionomics of Leptochilus (Euleptochilus) limbiferus (Morawitz 1867) (Hymenoptera: Vespidae: Eumeninae), with taxonomic notes and new records. 1124 records from Bases de datos del proyecto análisis de la riqueza y el endemismo de la flora de México, con fines de su conservación, usando grupos y métodos selectos. 30 records from Five new species and new records of the spider genus Stemmops (Araneae, Theridiidae, Spintharinae) from Brazil. 7 records from A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica.. 397 records from MCCC - Mendocino College Coast Center Herbarium. 19391 records from Ohio State University Tetrapod Division - Bird Collection (OSUM). 2 records from Coptus Wollaston (Coleoptera: Curculionidae: Cossoninae): A genus new to China with descriptions of two new species. 1 records from A new species of freshwater flatworm (Platyhelminthes, Tricladida, Dendrocoelidae) inhabiting a chemoautotrophic groundwater ecosystem in Romania. 4 records from Unraveling the species diversity and relationships in the Leptodactylus mystaceus complex (Anura: Leptodactylidae), with the description of three new Brazilian species. 196 records from Type Specimens Of Birds In The American Museum Of Natural History Part 12. Passeriformes: Ploceidae, Sturnidae, Buphagidae, Oriolidae, Dicruridae, Callaeidae, Grallinidae, Corcoracidae, Artamidae, Cracticidae, Ptilonorhynchidae, Cnemophilidae, Paradisaeidae, And Corvidae. 18255 records from Sistematización de la colección entomológica y actualización de la colección del herbario CHIP del Instituto de Historia Natural y Ecología (IHNE), Chiapas (Plantas). 21 records from Variation In The Epiproct Of Arsapnia Decepta Banks, 1897 (Plecoptera: Capniidae), With Comments On Arsapnia Coyote (Nelson & Baumann 1987). 2 records from A third species of Parakermania Vandel, 1973 (Isopoda: Oniscidea: Armadillidae) from China. 1000 records from nsmk_mm_2019. 1 records from
Keywords: GBIF; biodiversity; species occurrences